Semiconductor nanoparticles, preparation method therefor, and electroluminescent device and display device including

By forming a semiconductor nano -crystal layer containing zinc sulfide on the first particles, the problem of preparing high -efficiency glowing semiconductor nanoparticles in existing technologies has been solved, and nano particles with efficient lighting and long life have been achieved.

CN119370883APending Publication Date: 2025-01-28SAMSUNG ELECTRONICS CO LTD +1
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411004299.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2023-07-25
Filing Date
2024-07-25
Publication Date
2025-01-28

AI Technical Summary

Technical Problem

The prior art is difficult to effectively prepare semiconductor nanoparticles with high-efficiency luminescent properties, especially in the formation of high-quality semiconductor nanocrystal layers.

Method used

By contacting the zinc forehead and sulfur prelimation at the predetermined temperature, it forms a semiconductor nanocrystalline layer containing zinc sulfide on the first particle to prepare semiconductor nanoparticles with efficient light -emitting performance.

Benefits of technology

The efficient lighting performance of semiconductor nanoparticles, including absolute quantum production rates greater than or equal to 90%, and improved lighting efficiency, and significantly improved the performance and life of the device in electronic devices.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119370883A_ABST
    Figure CN119370883A_ABST
Patent Text Reader

Abstract

Semiconductor nanoparticles, a method of preparing the semiconductor nanoparticles, and an electroluminescent device and a display device including the semiconductor nanoparticles. A method of making semiconductor nanoparticles includes contacting a zinc precursor and a sulfur precursor in the presence of a first particle at a predetermined temperature to form a semiconductor nanocrystal layer containing zinc sulfide on the first particle, where the first particle includes a Group II-VI compound comprising zinc, selenium, and optionally tellurium, or the first particle includes a Group III-V compound including indium and phosphorus. The predetermined temperatures include (e.g., are) a temperature greater than 300 DEG C and less than or equal to about 380 DEG C (e.g., reaction temperature), and the sulfur precursor includes a C3 (e.g., C9) to C50 thiol compound, or a combination thereof.
Need to check novelty before this filing date? Find Prior Art

Description

[0001] CROSS-REFERENCE TO RELATED APPLICATIONS

[0002] This application claims the priority of Korean Patent Application No. 10-2023-0097055 filed in the Korean Intellectual Property Office on July 25, 2023, and all rights and interests arising therefrom, the contents of which are incorporated herein by reference in their entirety. Technical Field

[0003] The present disclosure relates to a method for manufacturing semiconductor nanoparticles, semiconductor nanoparticles manufactured by the method, and devices (eg, electroluminescent devices) and display apparatuses including the semiconductor nanoparticles. Background Art

[0004] Semiconductor nanoparticles (e.g., semiconductor nanocrystal particles) can emit light. For example, quantum dots including semiconductor nanocrystals can exhibit a quantum confinement effect, and when electrons in an excited state transition from a conduction band to a valence band as a result of light excitation or an applied voltage, light emission from the semiconductor nanoparticles can occur. By adjusting the size and / or composition of the semiconductor nanoparticles, the semiconductor nanoparticles can be configured to emit light in a desired wavelength region.

[0005] The semiconductor nanoparticles may be used in light emitting devices (eg, electroluminescent devices) and display devices including the semiconductor nanoparticles. Summary of the invention

[0006] Embodiments provide methods for preparing semiconductor nanoparticles.

[0007] The embodiment provides semiconductor nanoparticles that can be prepared by the preparation method.

[0008] Embodiments provide a light emitting device configured to emit light with or without an additional light source, for example, by applying a voltage to the semiconductor nanoparticles.

[0009] Embodiments provide a display device (e.g., a quantum dot-light emitting diode (QD-LED) display) that includes a light emitting material having a nanostructure (e.g., nanoparticles such as semiconductor nanoparticles) in a configuration of blue pixels, red pixels, and / or green pixels.

[0010] The embodiment provides semiconductor nanoparticles which may be included in the light emitting device of the embodiment.

[0011] Embodiments provide a display device including the semiconductor nanoparticles.

[0012] In an embodiment, a method for preparing semiconductor nanoparticles includes contacting a zinc precursor and a sulfur precursor in the presence of a first particle at a predetermined temperature to form a semiconductor nanocrystal layer containing zinc sulfide on the first particle, for example, the contacting results in a reaction between the zinc precursor and the sulfur precursor. The first particle includes a II-VI compound including zinc and selenium. The II-VI compound (or the first particle) may further include tellurium (or a II-VI compound including zinc, selenium and tellurium). The predetermined temperature includes a temperature greater than or equal to about 300° C. and less than or equal to about 380° C. (e.g., a reaction temperature).

[0013] The sulfur precursor includes a thiol compound (e.g., a monothiol compound) of C3 (e.g., C8 or C9) to C50 (or C10-C24 or C12-C18) or a combination thereof. The sulfur precursor (or the thiol compound) may include a C3-C30 (C8-C12 or C14) branched hydrocarbon group (thiol compound having the hydrocarbon group).

[0014] The sulfur precursor may or may not include sulfur-trioctylamine (S-TOA), sulfur-trioctylphosphine (S-TOP), sulfur-octadecene (S-ODE), sulfur-tributylphosphine (S-TBP), sulfur-triphenylphosphine (S-TPP), bis(trialkylsilyl)sulfide (e.g., bis(trimethylsilyl)sulfide), trialkylsilylalkylsulfide (e.g., trimethylsilylmethylsulfide), or a combination thereof.

[0015] The sulfur precursor may not include a sulfur-hydrocarbon solvent adduct.

[0016] The first particles may further include a III-V compound. The III-V compound may include indium and phosphorus.

[0017] The first particle or the semiconductor nanoparticle may include a first semiconductor nanocrystal and a second semiconductor nanocrystal. The first semiconductor nanocrystal may include a II-VI compound including zinc, selenium, and tellurium; or a III-V compound including indium and phosphorus. The second semiconductor nanocrystal may include a II-VI compound including zinc and selenium.

[0018] In an embodiment, the first semiconductor nanocrystal may include a II-VI group compound including zinc, selenium, and tellurium, and the second semiconductor nanocrystal may include a II-VI group compound including zinc and selenium. In an embodiment, the first semiconductor nanocrystal may include a III-V group compound including indium and phosphorus, and the second semiconductor nanocrystal may include a II-VI group compound including zinc and selenium.

[0019] The second semiconductor nanocrystal may be disposed between the first semiconductor nanocrystal (eg, first semiconductor nanocrystal layer) and the semiconductor nanocrystal layer.

[0020] The method may further include adding the first particles, the zinc precursor, and the sulfur precursor to a reaction medium including an organic solvent at a first temperature.

[0021] The reaction medium may be pretreated under vacuum at a temperature of about 80°C to about 180°C.

[0022] Prior to being added to the reaction medium, the first particles may be washed with an organic solvent and then dispersed in a dispersing solvent.

[0023] The first temperature may be greater than or equal to about 180° C., or greater than or equal to about 200° C. The first temperature may be less than or equal to the predetermined temperature (e.g., a temperature for a reaction between the sulfur precursor and the zinc precursor). The first temperature may be less than or equal to about 340° C., less than or equal to about 320° C., less than or equal to about 319° C., or less than or equal to about 280° C.

[0024] The predetermined temperature (or the reaction temperature) may be greater than or equal to about 315°C and less than or equal to about 319°C.

[0025] The predetermined temperature (or the reaction temperature) may be greater than or equal to about 336°C and less than or equal to about 360°C.

[0026] The sulfur precursor may include a compound (thiol compound) (e.g., represented by R-SH, wherein R is a substituted or unsubstituted C3 (e.g., C8 or C9) to C50 aliphatic straight or branched hydrocarbon group, for example, an alkyl, alkenyl, or alkynyl group). In an embodiment, R of the thiol compound may be a C8-C24 branched aliphatic hydrocarbon group.

[0027] The sulfur precursor may include octanethiol, ethylhexanethiol (eg, 2-ethylhexanethiol), decanethiol, undecanethiol, dodecanethiol, tetradecanethiol, hexadecanethiol, octadecanethiol, or a mixture thereof.

[0028] The zinc precursor may include a zinc carboxylate having a substituted or unsubstituted C1-C60 or C5-C40 aliphatic hydrocarbon group.

[0029] The zinc precursor may include a compound represented by Chemical Formula 1:

[0030] Chemical formula 1

[0031] ACOO-Zn-OOCB

[0032] In Chemical Formula 1, A and B are the same or different and are each independently a substituted or unsubstituted linear or branched C1-C60 aliphatic hydrocarbon group (eg, an alkyl, alkenyl or alkynyl group), or a substituted or unsubstituted C3-C50 or C6-C30 aromatic hydrocarbon group.

[0033] In Chemical Formula 1, A and B are the same or different and are each independently a substituted or unsubstituted C1-C11 or C4-C8 linear or branched aliphatic hydrocarbon group, a substituted or unsubstituted C12-C60 or C16-24 linear or branched aliphatic hydrocarbon group, or a combination thereof.

[0034] In Chemical Formula 1, A and B are the same or different and are each independently ethylhexyl, methylbutyl (e.g., 2-methylbutyl, 3-methylbutyl), hexyldecyl (2-hexyldecyl), oleyl, myristyl, stearyl, lauryl, or a combination thereof.

[0035] In an embodiment, the semiconductor nanoparticles include a first organic ligand and a second organic ligand, the first organic ligand including a C12 or higher carboxylate moiety (carboxylic acid group moiety) (e.g., derived from a zinc carboxylate such as zinc oleate), the second organic ligand including a thiol moiety (thiol group moiety) (e.g., derived from a thiol compound), and in GC-MS (gas chromatography-mass spectrometry) analysis, the peak area of ​​the second organic ligand may be greater than or equal to about 0.01%, greater than or equal to about 0.1%, or greater than or equal to about 0.5% and less than or equal to about 17% of the total area of ​​the peaks of the first organic ligand and the second organic ligand.

[0036] In an embodiment, in a thermogravimetric analysis, the semiconductor nanoparticles may exhibit a residual weight of greater than or equal to about 85 wt %, greater than or equal to about 86 wt %, or greater than or equal to about 87 wt % of the total weight of the semiconductor nanoparticles. In an embodiment, as determined by thermogravimetric analysis, the semiconductor nanoparticles may exhibit an organic content of less than or equal to about 14 wt %, less than or equal to about 13 wt %, or less than or equal to about 12 wt %. As determined by thermogravimetric analysis, the derivative (differential) thermogravimetric curve of the semiconductor nanoparticles may exhibit a peak at a temperature between about 200° C. and about 300° C. The derivative thermogravimetric curve of the semiconductor nanoparticles may further exhibit a peak at a temperature between about 300° C. or about 400° C. and about 500° C.

[0037] The semiconductor nanoparticles may not include cadmium.

[0038] In an embodiment, the semiconductor nanoparticles include zinc, selenium, tellurium, and sulfur, and do not include cadmium. The semiconductor nanoparticles are configured to emit blue light, the semiconductor nanoparticles have an absolute quantum yield greater than or equal to about 90%, and in the semiconductor nanoparticles, the molar ratio of zinc to selenium (Zn:Se) is greater than or equal to about 1:1 and less than or equal to about 3:1, or less than or equal to about 2.3:1, and the molar ratio of sulfur to tellurium (S:Te) is greater than or equal to about 10:1, or greater than 73:1 and less than or equal to about 180:1. The semiconductor nanoparticles may include a semiconductor nanocrystal layer including zinc sulfide.

[0039] The semiconductor nanoparticles may include a first semiconductor nanocrystal and a second semiconductor nanocrystal, the first semiconductor nanocrystal may include a II-VI compound including zinc, selenium and tellurium, and the second semiconductor nanocrystal may include a II-VI compound including zinc and selenium. The second semiconductor nanocrystal may be disposed between the first semiconductor nanocrystal (e.g., a first semiconductor nanocrystal layer) and the semiconductor nanocrystal layer. The details of the semiconductor nanoparticles are the same as described herein.

[0040] The blue light may have a peak emission wavelength greater than or equal to about 440 nm, or greater than or equal to about 450 nm and less than about 480 nm, or less than or equal to about 479 nm.

[0041] The peak emission wavelength may be greater than or equal to about 455 nm and less than or equal to about 475 nm, greater than or equal to about 460 nm and less than or equal to about 473 nm, greater than or equal to about 466 nm and less than or equal to about 472 nm, greater than or equal to about 468 nm and less than or equal to about 470 nm, or a combination thereof.

[0042] The absolute quantum yield may be greater than or equal to about 91% and less than or equal to about 99%, greater than or equal to about 93% and less than or equal to about 98%, or greater than or equal to about 95% and less than or equal to about 96%, or any combination of the recited greater and lesser values.

[0043] The semiconductor nanoparticles may have a size or an average size (hereinafter, "size") greater than or equal to about 7 nm, greater than or equal to about 8 nm, greater than or equal to about 9 nm, or greater than or equal to about 10 nm and less than or equal to about 13 nm, less than or equal to about 11 nm, or less than or equal to about 10.2 nm.

[0044] The semiconductor nanoparticles may have a solidity or average solidity (hereinafter, simply referred to as “solidity”) greater than or equal to about 0.975.

[0045] In the semiconductor nanoparticles, the molar ratio of zinc to selenium (Zn:Se) may be less than or equal to about 2.5:1, less than or equal to about 2.1:1, less than or equal to about 2:1, less than or equal to about 1.9:1 and greater than or equal to about 1.2:1, greater than or equal to about 1.5:1, or greater than or equal to about 1.7:1.

[0046] In the semiconductor nanoparticles, a molar ratio of sulfur to tellurium (S:Te) may be greater than or equal to about 50:1, or greater than or equal to about 65:1.

[0047] In the semiconductor nanoparticles, a molar ratio of sulfur to tellurium (S:Te) may be less than or equal to about 200:1, less than or equal to about 180:1, less than or equal to about 160:1, or less than or equal to about 110:1.

[0048] In the semiconductor nanoparticles, a molar ratio of sulfur to the sum of sulfur and selenium (S:(S+Se)) may be greater than or equal to about 0.3:1 and less than or equal to about 0.5:1.

[0049] In an embodiment, the semiconductor nanoparticles include indium, phosphorus, zinc, selenium, and sulfur, the semiconductor nanoparticles do not include cadmium, and the semiconductor nanoparticles include a semiconductor nanocrystal layer including zinc sulfide, and the semiconductor nanoparticles may be configured to emit green light.

[0050] The semiconductor nanoparticles may include a first semiconductor nanocrystal and a second semiconductor nanocrystal. The first semiconductor nanocrystal may include a III-V compound comprising indium and phosphorus. The second semiconductor nanocrystal may include a II-VI compound comprising zinc and selenium. The second semiconductor nanocrystal may be disposed between the first semiconductor nanocrystal (e.g., a first semiconductor nanocrystal layer) and the semiconductor nanocrystal layer. The details of the semiconductor nanoparticles are the same as described herein.

[0051] The green light may have a peak emission wavelength greater than or equal to about 480 nm and less than or equal to about 580 nm.

[0052] The semiconductor nanoparticles may have an absolute quantum yield of greater than or equal to about 90%, greater than or equal to about 91% and less than or equal to about 99%, greater than or equal to about 93% and less than or equal to about 98%, greater than or equal to about 95% and less than or equal to about 96%, or a combination thereof.

[0053] In the semiconductor nanoparticles, a molar ratio of zinc to indium (Zn:In) may be greater than or equal to about 60:1 and less than or equal to about 250:1, greater than or equal to about 70:1 and less than or equal to about 120:1, or a combination thereof.

[0054] In the semiconductor nanoparticles, a molar ratio of indium to a sum of selenium and sulfur (In:(Se+S)) may be greater than or equal to about 0.0001:1 and less than or equal to about 0.03:1.

[0055] In the semiconductor nanoparticles, a molar ratio of sulfur to selenium (S:Se) may be less than or equal to about 0.5:1.

[0056] The semiconductor nanoparticles may have a size or average size greater than or equal to about 7.5 nm and less than or equal to about 20 nm, greater than or equal to about 8 nm and less than or equal to about 10 nm, or a combination thereof, and optionally, the semiconductor nanoparticles may have a particle size distribution exhibiting a standard deviation of less than or equal to about 10% of the average particle size.

[0057] In an embodiment, an electroluminescent device includes: a first electrode and a second electrode, for example, spaced apart from each other (for example, each electrode has a surface opposite to the other); and a light-emitting layer disposed between the first electrode and the second electrode, wherein the light-emitting layer includes semiconductor nanoparticles.

[0058] In an embodiment, the light emitting layer (or the semiconductor nanoparticles) may be configured to emit blue light. In an embodiment, the light emitting layer (or the semiconductor nanoparticles) may be configured to emit green light.

[0059] In the light emitting layer, an amount of chlorine may be less than or equal to about 1.4 atomic %, less than or equal to about 1.2 atomic %, or less than or equal to about 0.8 atomic % based on all elements of the light emitting layer.

[0060] The electroluminescent device may have a maximum external quantum efficiency (EQE) of greater than or equal to about 8%, greater than or equal to about 10%, greater than or equal to about 11%, or greater than or equal to about 12%. The electroluminescent device may have a maximum external quantum efficiency (EQE) of greater than or equal to about 60,000 candelas per square meter (cd / m 2 ), greater than or equal to about 80,000 cd / m 2 , greater than or equal to about 90,000cd / m 2 , or greater than or equal to about 100,000 cd / m 2 Maximum brightness.

[0061] The light emitting layer may be configured to emit blue light at 650 cd / m 2 The electroluminescent device operated at an initial brightness of 100 nits may have a T90 of greater than or equal to about 20 hours, greater than or equal to about 25 hours, greater than or equal to about 30 hours, or greater than or equal to about 40 hours.

[0062] The electroluminescent device operated at an initial brightness of 650 nits may have a T50 of greater than or equal to about 70 hours, greater than or equal to about 80 hours, greater than or equal to about 90 hours, or greater than or equal to about 170 hours.

[0063] In an embodiment, the light-emitting layer may be configured to emit green light, and the electroluminescent device may exhibit a T90 of greater than or equal to about 60 hours, greater than or equal to about 80 hours, or greater than or equal to about 120 hours at an initial operating brightness of 2700 nits; or the electroluminescent device may exhibit a T90 of greater than or equal to about 500 hours at an initial operating brightness of 1000 nits.

[0064] In an embodiment, a photoluminescent device comprises a light-emitting layer including the semiconductor nanoparticles; and a light source, and the light source is configured to provide incident light to the light-emitting layer. In the light-emitting layer, the semiconductor nanoparticles may be dispersed in a matrix (e.g., a polymer matrix including an insulating polymer).

[0065] In an embodiment, a display device includes the semiconductor nanoparticles, the electroluminescent device, the photoluminescent device, or a combination thereof. The display device may include or may include a VR device, an AR device, a mobile terminal device, a monitor, a computer (e.g., a laptop or a tablet), a television, an electronic sign (electronics), a camera, or an electronic component for a car.

[0066] According to the manufacturing method of the embodiment, on the nanoparticles including the core including the III-V compound or the II-VI compound and the (semiconductor nanocrystal) layer including the zinc sulfide based on the II-VI group, the semiconductor nanocrystal layer including zinc sulfide can be easily formed with the efficiency or the rate of improvement. For example, the semiconductor nanoparticles have an increased particle size, and the formed semiconductor nanocrystal layer can show improved coating (coating) quality. The semiconductor nanoparticles prepared according to the method of the embodiment can show improved shape parameters. In an embodiment, the semiconductor nanoparticles can include a limited amount of ligands derived from thiol, and when the semiconductor nanoparticles are applied to electronic devices such as electroluminescent devices, the electronic devices can show improved device performance (for example, improved luminous efficiency and / or improved life).

[0067] The semiconductor nanoparticles can be used in a variety of display devices and biomarkers (e.g., biosensors or bioimaging), photodetectors, solar cells, or hybrid composites. In an embodiment, when applied to a display device, such as used in a display device, the light emitting device or the electroluminescent device can contribute to the realization of improved display quality, such as providing. BRIEF DESCRIPTION OF THE DRAWINGS

[0068] The above and other advantages and features of the present disclosure will become more apparent by further describing exemplary embodiments thereof in detail with reference to the accompanying drawings, in which:

[0069] Figure 1 A flow chart illustrating a process for preparing semiconductor nanoparticles according to an embodiment.

[0070] Figure 2 is a schematic cross-sectional view of an embodiment of a light emitting device.

[0071] Figure 3 is a schematic cross-sectional view of an embodiment of a light emitting device.

[0072] Figure 4 is a schematic cross-sectional view of an embodiment of a light emitting device.

[0073] Figure 5A The results of GC-MS analysis of the semiconductor nanoparticles prepared in Synthesis Example 1-1(A), Synthesis Example 1-2(B), and Comparative Synthesis Example 2-1(C) are described.

[0074] Figure 5B The results of GC-MS analysis of the semiconductor nanoparticles prepared in Comparative Synthesis Example 3 are described. DETAILED DESCRIPTION

[0075] The advantages and features of the present disclosure, and methods for achieving the same, will become apparent with reference to the following example embodiments, together with the accompanying drawings attached hereto. However, the present invention may be embodied in many different forms, and the embodiments should not be construed as being limited to the embodiments set forth herein. On the contrary, these embodiments are provided so that the present disclosure will be thorough and complete, and will fully convey the scope of the present invention to those skilled in the art.

[0076] If not otherwise defined, all terms (including technical and scientific terms) in the specification are used as commonly understood by those of ordinary skill in the art. It will be further understood that terms, such as those defined in commonly used dictionaries, should be interpreted as having meanings consistent with their context in the relevant field and should not be interpreted ideally or exaggeratedly unless clearly defined. The terms used herein are for the purpose of describing specific embodiments and are not intended to be limiting.

[0077] As used herein, the singular forms "one (kind) (indefinite article) (a, an)" and "the" are intended to include plural forms, including "at least one (kind)", unless the content clearly indicates otherwise. For example, "element" has the same meaning as "at least one (kind) element", unless the context clearly indicates otherwise. Therefore, as used herein, the word "nanoparticle" may refer to a single nanoparticle or a plurality of nanoparticles. For example, the word "semiconductor nanoparticle" may refer to a single semiconductor nanoparticle or a plurality of semiconductor nanoparticles. "At least one (kind)" will not be interpreted as limiting "one (kind)". "Or" means "and / or". As used herein, the term "and / or" includes any and all combinations of one or more of the relevant listed items.

[0078] It will be further understood that the terms “comprise” or “include” when used in this specification indicate the presence of stated features, regions, integers, steps, operations, elements and / or components, but do not exclude the presence or addition of one or more additional features, regions, integers, steps, operations, elements, components, and / or combinations thereof.

[0079] In the accompanying drawings, the thickness of layers, films, panels, regions, etc. is exaggerated for clarity. The same reference numerals represent the same elements throughout the specification. It will be understood that when an element such as a layer, film, region, or substrate is referred to as being "on" another element, it may be directly on the other element or there may be an intermediate element. Conversely, when an element is referred to as being "directly on" another element, there is no intermediate element. In order to clearly illustrate the embodiments in the accompanying drawings, some parts that are not really relevant to the description may be omitted.

[0080] It will be understood that although the terms "first", "second", "third", etc. may be used herein to describe various elements, components, regions, layers and / or parts, these elements, components, regions, layers and / or parts should not be limited by these terms. These terms are only used to distinguish one element, component, region, layer or part from another element, component, region, layer or part. Therefore, without departing from the teachings herein, the "first element", "component", "region", "layer" or "part" discussed below may be referred to as a second element, component, region, layer or part.

[0081] As used herein, the term "cross-section" means a situation in which a cross section of a given object is cut (eg, in a substantially vertical direction) and is observed in a lateral direction.

[0082] Hereinafter, the value of the work function, conduction band, or lowest unoccupied molecular orbital (LUMO) (or valence band, or highest occupied molecular orbital (HOMO)) energy level is expressed as an absolute value from the vacuum energy level. In addition, when the work function or energy level is referred to as "deep", "high" or "large", the work function or energy level has a large absolute value based on the vacuum energy level of "0 electron volt (eV)", and when the work function or energy level is referred to as "shallow", "low" or "small", the work function or energy level has a small absolute value based on the vacuum energy level of "0 eV".

[0083] As used herein, the term "Group" may refer to a Group of the periodic table.

[0084] As used herein, “Group III” refers to Group IIIA and Group IIIB, and examples of Group IIIA metals may be Al, In, Ga, or Tl, and examples of Group IIIB may be scandium or yttrium, but are not limited thereto.

[0085] As used herein, "Group V" includes Group VA and includes nitrogen, phosphorus, arsenic, antimony, or bismuth, but is not limited thereto.

[0086] As used herein, average may be a mean or a median. In embodiments, average may be a mean.

[0087] As used herein, when no definition is otherwise provided, "substituted" refers to a compound, group, or portion of hydrogen being replaced by a substituent such as a C1-C30 alkyl, a C2-C30 alkenyl, a C2-C30 alkynyl, a C2-C30 epoxy, a C2-C30 alkyl ester group, a C3-C30 alkenyl ester group (e.g., an acrylate group, a methacrylate group), a C6-C30 aryl, a C7-C30 alkylaryl, a C1-C30 alkoxyl, a C1-C30 heteroalkyl, a C3-C30 heteroalkylaryl, a C3-C30 cycloalkyl, a C3-C15 cycloalkenyl, a C6-C30 cycloalkynyl, a C2-C30 heterocycloalkyl, a halogen (-F, -Cl, -Br, or -I), a hydroxyl (-OH), a nitro (-NO), or a cycloalkyl. 2 ), cyano (-CN), amino (-NRR', wherein R and R' are each independently hydrogen or C1-C6 alkyl), azido (-N 3 ), amidino (-C(=NH)NH 2 ), hydrazino (-NHNH 2 ), hydrazone (=N(NH 2 )), aldehyde group (-C(=O)H), carbamoyl group (-C(O)NH 2), thiol group (-SH), ester group (-C(=O)OR, wherein R is C1-C6 alkyl or C6-C12 aryl), carboxyl group (-COOH) or its salt (-C(=O)OM, wherein M is an organic or inorganic cation), sulfonic acid group (-SO 3 H) or its salt (-SO 3 M, where M is an organic or inorganic cation), a phosphate group (-PO 3 H 2 ) or its salt (-PO 3 MH or -PO 3 M 2 , wherein M is an organic or inorganic cation), or a combination thereof.

[0088] As used herein, when no definition is provided in addition, "hydrocarbon" and "hydrocarbon group" refer to compounds or groups (e.g., alkyl, alkenyl, alkynyl, or aryl) comprising carbon and hydrogen. A hydrocarbon group may be a group having a monovalent or higher valence formed by removing a hydrogen atom, such as greater than or equal to about one hydrogen atom, from an alkane, alkene, alkyne, or aromatic hydrocarbon. In a hydrocarbon or hydrocarbon group, a methylene group, such as at least one methylene group, may be replaced by an oxygen moiety, a carbonyl moiety, an ester moiety, -NH-, or a combination thereof. Unless otherwise indicated to the contrary, a hydrocarbon compound or hydrocarbon group (alkyl, alkenyl, alkynyl, or aryl) may have 1-60, 2-32, 3-24, or 4-12 carbon atoms.

[0089] As used herein, when no definition is otherwise provided, "aliphatic" refers to a saturated or unsaturated straight chain or branched hydrocarbon or hydrocarbon group. An aliphatic group may be, for example, an alkyl, alkenyl, or alkynyl group.

[0090] As used herein, when no definition is otherwise provided, "alkyl" refers to a straight-chain or branched saturated monovalent hydrocarbon group (methyl, ethylhexyl, etc.).

[0091] As used herein, when a definition is not otherwise provided, "alkenyl" refers to a straight-chain or branched monovalent hydrocarbon group having a carbon-carbon double bond.

[0092] As used herein, when a definition is not otherwise provided, "alkynyl" refers to a straight-chain or branched monovalent hydrocarbon group having a carbon-carbon triple bond.

[0093] As used herein, when a definition is not otherwise provided, "aryl" refers to a group formed by removing hydrogen, for example, at least one hydrogen, from an aromatic hydrocarbon (eg, phenyl or naphthyl).

[0094] As used herein, when no definition is otherwise provided, "hetero" means including 1 to 3 heteroatoms, for example, N, O, S, Si, P, or a combination thereof.

[0095] In an embodiment, “aromatic” or “aromatic group” may include a C6-C30 aromatic group (eg, composed of carbon and hydrogen) or an aromatic ring including a heteroatom (eg, a C3-C30 heteroaryl group).

[0096] The term "alicyclic group" refers not only to a saturated or unsaturated C3-C30 cyclic group composed of carbon and hydrogen but also to a saturated or unsaturated C3-C30 heterocyclic group further including a heteroatom in addition to carbon and hydrogen.

[0097] As used herein, when a definition is not otherwise provided, "alkoxy" means an alkyl group linked through an oxygen group (ie, alkyl-O-), for example, methoxy, ethoxy, or sec-butoxy.

[0098] As used herein, when no definition is otherwise provided, an "amine group" may be represented by -NRR, wherein each R is independently hydrogen, a C1-C12 alkyl group, a C7-C20 alkylaryl group, a C7-C20 arylalkyl group, or a C6-C18 aryl group.

[0099] As used herein, the expression "does not include cadmium (or other harmful heavy metals)" may refer to the following: wherein the concentration of each cadmium (or other heavy metals considered harmful) may be less than or equal to about 100 parts per million by weight (ppmw), less than or equal to about 50 ppmw, less than or equal to about 10 ppmw, less than or equal to about 1 ppmw, less than or equal to about 0.1 ppmw, less than or equal to about 0.01 ppmw, or zero. In an embodiment, substantially no cadmium (or other heavy metal) may be present, or if present, the amount of cadmium (or other heavy metal) may be less than or equal to the detection limit of a given analytical tool (e.g., inductively coupled plasma atomic emission spectrometry) or as its impurity level.

[0100] In embodiments, the numerical ranges stated herein include the endpoints of each range. As used herein, the upper and lower endpoints stated for the various numerical values ​​can be independently combined to provide a range.

[0101] As used herein, "about" includes the stated value and means within an acceptable range of deviation for the particular value as determined by one of ordinary skill in the art taking into account the measurement in question and the errors associated with the measurement of the particular quantity (i.e., the limitations of the measurement system). For example, "about" may mean within one or more standard deviations of the stated value, or within ±10%, ±5%.

[0102] As used in this article, nanoparticle or nanostructure are to have at least one region or characteristic scale having nanometer scale (size).In embodiments, the scale (or average scale) of nanoparticle is less than or equal to about 500 nanometers (nm), less than or equal to about 300nm, less than or equal to about 250nm, less than or equal to about 150nm, less than or equal to about 100nm, less than or equal to about 50nm or less than or equal to about 30nm, and can be greater than about 0.1nm or about 1nm.In embodiments, described structure can have any suitable shape.

[0103] Nanoparticles (e.g., semiconductor nanoparticles) may include nanowires, nanorods, nanotubes, branched nanostructures, nanotetrapods, nanotripods, nanobipods, nanodots, or multipod-like shapes such as at least two feet, and are not limited thereto. The nanoparticles may be, for example, substantially crystalline, substantially monocrystalline, polycrystalline, (e.g., at least partially) amorphous, or a combination thereof.

[0104] Semiconductor nanoparticles (e.g., quantum dots) may exhibit quantum confinement or exciton confinement effects. Quantum dots are a type of luminescent nanostructure. As used herein, the shape of "quantum dots" may not be particularly limited. In this specification, the terms "nanoparticles" or "quantum dots" are not limited in their shape unless specifically defined. Semiconductor nanoparticles may have a size smaller than the Bohr excitation diameter in bulk crystals of the same material. By controlling the size of the emission center of the nanocrystal, semiconductor nanoparticles may emit light of a wavelength corresponding to their band gap energy.

[0105] As used herein, T50 refers to the time taken for the brightness (or photocurrent) of the device to decrease to 50% of the initial brightness (or initial photocurrent) when the device is initially driven at a predetermined initial brightness.

[0106] As used herein, T90 refers to the time taken for the brightness (or photocurrent) of the device to decrease to 90% of the initial brightness (or initial photocurrent) when the device is initially driven at a predetermined initial brightness.

[0107] As used herein, external quantum efficiency (EQE) refers to the ratio of the number of photons emitted from a light emitting diode (LED) to the number of electrons passing through the device. EQE may be a measure of how efficiently a light emitting diode converts electrons into emitted photons. In an embodiment, EQE may be determined based on the following equation:

[0108] EQE = (injection efficiency) × (solid-state quantum yield) × (extraction efficiency)

[0109] in

[0110] Injection efficiency is the fraction of electrons passing through the device that are injected into the active region;

[0111] The solid-state quantum yield is the fraction of all electron-hole recombination in the active region that is radiative and produces photons; and

[0112] The extraction efficiency is the fraction of photons generated in the active region that escape from the device.

[0113] In this article, the maximum external quantum efficiency refers to the maximum value of the external quantum efficiency.

[0114] In this article, maximum brightness refers to the maximum value of the brightness that a device can achieve.

[0115] As used herein, quantum efficiency is a term used interchangeably with quantum yield. Quantum efficiency (or quantum yield) can be measured in solution or in the solid state (with a complex). In an embodiment, quantum efficiency (or quantum yield) is the ratio of the photons emitted by a nanostructure or its group to the photons absorbed by it. In an embodiment, quantum efficiency can be measured by any suitable method. For example, for fluorescence quantum yield or efficiency, there can be two methods: absolute method and relative method.

[0116] In the absolute method, the quantum efficiency is obtained by detecting the fluorescence of all samples by an integrating sphere. In the relative method, the quantum efficiency of an unknown sample is calculated by comparing the fluorescence intensity of a standard dye (standard sample) with the fluorescence intensity of an unknown sample. Coumarin 153, coumarin 545, rhodamine 101 inner salt, anthracene, and rhodamine 6G can be used as standard dyes according to their photoluminescence (PL) wavelengths, but the present disclosure is not limited thereto.

[0117] The band gap energy of semiconductor nanocrystal particles can change according to the size, structure and composition of nanocrystal.Semiconductor nanocrystal can be used as luminescent material in display equipment, energy equipment or bioluminescent equipment in various fields.Semiconductor nanoparticles (for example, quantum dots) configured to present luminescence (for example, electroluminescence or photoluminescence) properties under the actual applicable, for example desirable level can contain harmful heavy metals such as cadmium (Cd), lead, mercury or its combination.Therefore, it is desirable to provide a light emitting device or display equipment with a luminescent layer that is substantially free of harmful heavy metals.

[0118] The semiconductor nanoparticles according to the embodiment are environmentally friendly, and can emit blue light with a desired wavelength with improved luminous efficiency, and can exhibit improved stability in an external environment. The electroluminescent device according to the embodiment includes the semiconductor nanoparticles, and is a self-emitting light-emitting device configured to emit desired light by applying a voltage, for example, with or without a light (radiation) source. From an environmental point of view, the light-emitting device and display device of the embodiment are desirable.

[0119] The semiconductor nanoparticles in the embodiments include a II-VI compound including zinc, selenium, and optionally tellurium (or a first particle including the II-VI compound). The semiconductor nanoparticles further include a semiconductor nanocrystal layer including zinc and sulfur (or including zinc sulfide). The semiconductor nanocrystal layer may be disposed on the first particle. The first particle may further include a III-V compound. The III-V compound may include indium and phosphorus. The III-V compound may further include zinc.

[0120] The first particles may include first semiconductor nanocrystals and second semiconductor nanocrystals, the first semiconductor nanocrystals may include a Group II-VI compound including zinc, selenium, and tellurium or a Group III-V compound including indium and phosphorus, and the second semiconductor nanocrystals may include a Group II-VI compound including zinc and selenium.

[0121] The second semiconductor nanocrystal may be disposed between the first semiconductor nanocrystal and the semiconductor nanocrystal layer.

[0122] The semiconductor nanoparticles may emit blue light or green light. The semiconductor nanoparticles may have an absolute quantum yield greater than or equal to about 90%. The absolute quantum yield may be greater than or equal to about 91% and less than or equal to about 99%, greater than or equal to about 93% and less than or equal to about 98%, greater than or equal to about 95% and less than or equal to about 96%, or a combination thereof.

[0123] The semiconductor nanoparticles may not include cadmium. The semiconductor nanoparticles may not include lead, mercury, or a combination thereof.

[0124] Semiconductor nanoparticles that do not contain cadmium (e.g., quantum dots that do not contain cadmium) can have a core-shell structure, e.g., with multiple shells. Such a structure can contribute to the realization of electroluminescent devices with higher efficiency and longer lifespan. Without wishing to be bound by any theory, for the application of electroluminescent devices based on quantum dots, the thickness of the shell of the semiconductor nanocrystal layer or semiconductor nanoparticle can be changed (e.g., increased or decreased), which is believed to be able to reduce the effect of energy transfer between quantum dots and reduce the ratio of ligands.

[0125] However, the inventor has found that along with the size increase of semiconductor nanoparticles, it is more difficult to provide the semiconductor nanocrystal layer.The semiconductor nanocrystal layer may be included in the outermost shell of semiconductor nanoparticles or may constitute the outermost shell of semiconductor nanoparticles.The semiconductor nanocrystal layer may have a band gap energy that is for example larger than the band gap energy of the first particle or semiconductor nanocrystal contained therein, and may contain a material (for example, zinc sulfide) with relatively small lattice constant.The semiconductor nanocrystal layer may present a lattice mismatch such as with the intermediate shell layer (for example, the II-VI compound comprising zinc and selenium) contained in the first particle, and it is believed that such lattice mismatch may result in a significant reduction in the coating rate of the semiconductor nanocrystal layer on the first particle during the manufacture of semiconductor nanoparticles. Without wishing to be bound by any theory, a reduction in the coating rate of the semiconductor nanocrystal layer (e.g., when the layer will constitute the outermost layer of the nanoparticle) can lead to an increase in the amount of unreacted precursor (e.g., metal carboxylate) in the reaction system, and this can damage the surface of the first particle (or the intermediate shell contained therein), reducing the luminescent properties (e.g., photoluminescence quantum yield, PLQY) of the resulting semiconductor nanoparticle.

[0126] The semiconductor nanoparticles of the embodiment may include, for example, a semiconductor nanocrystal layer formed according to the method described herein. Surprisingly, the inventors have found that the semiconductor nanoparticles including a semiconductor nanocrystal layer formed by the method of the embodiment, when included in an electronic device, may contribute to allowing the electronic device, such as an electroluminescent device, to have improved luminescent properties and increased lifespan.

[0127] Thus, in an embodiment, a method of preparing semiconductor nanoparticles includes contacting a zinc precursor with a sulfur precursor in the presence of a first particle at a predetermined temperature (eg, the contacting results in a reaction of the two precursors) to form a semiconductor nanocrystal layer including zinc sulfide on the first particle. Figure 1 .

[0128] The first particles include a II-VI compound including zinc, selenium, and optionally tellurium. In the method of the embodiment, the predetermined temperature (or the temperature for the reaction) may include (or may be) a temperature greater than or equal to about 320° C. and less than or equal to about 380° C. The sulfur precursor may include a thiol compound, such as a monothiol compound, having a substituted or unsubstituted C3-C50, C6-C30, C8-24, C9-C40, C10-C36, C12-C18, or C14-C16 (aliphatic or aromatic) hydrocarbon group. The sulfur precursor or the thiol compound may include a substituted or unsubstituted C3-C50, C6-C30, C8-24, C9-C40, C10-C36, C12-C18, or C14-C16 linear or branched aliphatic hydrocarbon group, a substituted or unsubstituted C6-C30 aromatic hydrocarbon group, or a combination thereof. The aliphatic hydrocarbon group may include a branched C3-C30 (e.g., C8-C16 or C12-C14) aliphatic hydrocarbon group or a C8-C16 (e.g., C12-C14) aliphatic hydrocarbon group. The carbon number of the thiol compound or the sulfur precursor may be greater than or equal to about 3, greater than or equal to about 8, greater than or equal to about 9, greater than or equal to about 10, greater than or equal to about 11, or greater than or equal to about 12. The carbon number of the thiol compound or the sulfur precursor may be less than or equal to 50, less than or equal to about 40, less than or equal to about 35, or less than or equal to about 20.

[0129] The first semiconductor nanocrystal (sometimes referred to herein as a "core") may be suitably prepared, for example, by any suitable method. In an embodiment, the first semiconductor nanocrystal is commercially available or may be synthesized by any suitable method.

[0130] In an embodiment, the first semiconductor nanocrystal (or the core) includes a III-V compound including indium and phosphorus, and can be formed by a hot injection method in which a solution including a metal precursor, such as an indium precursor and optionally a ligand, is heated at a high temperature (e.g., heated to a temperature greater than or equal to about 200° C.), and a phosphorus precursor is injected into a reaction flask. In an embodiment, the first semiconductor nanocrystal can be prepared by injecting a phosphorus precursor into a heated reaction medium including an indium precursor (wherein the heated medium (flask) is at a predetermined temperature) to provide a reaction system, and then increasing the temperature of the resulting reaction system to a reaction temperature.

[0131] The type of the indium precursor is not particularly limited and can be suitably selected. The indium precursor may include, but is not limited to, trimethyl indium, indium acetate, indium hydroxide, indium chloride, indium oxide, indium nitrate, and indium sulfate. The type of the phosphorus precursor is not particularly limited and can be suitably selected. The phosphorus precursor may include, but is not limited to, tri(trimethylsilyl)phosphine, tri(dimethylamino)phosphine, triethylphosphine, tributylphosphine, trioctylphosphine, triphenylphosphine, tricyclohexylphosphine, or a combination thereof.

[0132] In an embodiment, the first semiconductor nanocrystal or the core may include a first zinc chalcogenide including zinc, selenium, and tellurium. The first semiconductor nanocrystal or the core may be prepared by a method comprising:

[0133] A zinc precursor solution including a zinc precursor and an organic ligand is prepared; a selenium precursor and a tellurium precursor are prepared; the zinc precursor solution is heated to a core forming reaction temperature; and the selenium precursor, the tellurium precursor, and optionally the organic ligand are added to the zinc precursor solution, and a core forming reaction is performed. The types of zinc, selenium, and tellurium precursors are described herein.

[0134] In the core formation reaction, the ratio between the precursors (e.g., the molar ratio between zinc and selenium precursors, the molar ratio of tellurium precursor to selenium precursor), or the reaction time can be appropriately selected taking into account the desired peak emission wavelength of the resulting semiconductor nanoparticles, the reactivity of the precursors, the reaction temperature, or a combination thereof.

[0135] The reaction time for core formation is not particularly limited and can be selected accordingly. The reaction time for core formation can be adjusted based on the desired core size, the reactivity of the precursor, etc. The core formation reaction time can be in the range of about 1 minute to about 120 minutes, 5 minutes to about 100 minutes, about 10 minutes to about 80 minutes, about 15 minutes to about 60 minutes, about 25 minutes to about 45 minutes, about 30 minutes to about 35 minutes, or a combination thereof. The temperature of the core formation reaction is also not particularly limited and can be appropriately selected. For example, in the case of the first semiconductor nanocrystal based on indium phosphide, the core formation reaction temperature can be about 200°C to about 300°C, about 240°C to about 290°C, about 250°C to about 280°C, or a combination thereof. For example, in the case of the first semiconductor nanocrystal including the first zinc sulfide, the reaction temperature for core formation is about 200°C to about 340°C, for example, about 220°C to about 330°C. The reaction temperature for core formation may range from about 230°C to about 320°C, from about 240°C to about 310°C, from about 250°C to about 300°C, or any combination of the lower and higher temperatures set forth above.

[0136] The formed first semiconductor nanocrystals (eg, via a non-solvent precipitation method) may or may not be separated from the reaction system. The separated cores may be optionally washed and then added to a subsequent reaction.

[0137] In an embodiment, the first particle may further include a second semiconductor nanocrystal (e.g., disposed on the first semiconductor nanocrystal), and the second semiconductor nanocrystal may include a second zinc chalcogenide including zinc and selenium. The second zinc chalcogenide may further include or may not include sulfur. The second zinc chalcogenide may include zinc selenide, zinc selenide sulfide, or a combination thereof.

[0138] In an embodiment, the first particle comprises the second semiconductor nanocrystal and can be obtained by a method comprising:

[0139] A reaction medium including a zinc precursor, a solvent, and optionally an organic ligand is heated (or pretreated) under vacuum to a predetermined temperature (e.g., greater than or equal to about 100°C and less than or equal to about 180°C), the atmosphere in the reactor is then changed to an inert gas atmosphere (e.g., an inert gas is added or flowed into the reaction system), the reaction system is heated to a reaction temperature, a first semiconductor nanocrystal and a selenium precursor (and optionally a sulfur precursor) are added to the reaction system (e.g., at an injection temperature), and a reaction is then carried out at the reaction temperature to obtain first particles including the second semiconductor nanocrystal.

[0140] In the method of the embodiment, the selenium precursor may be injected into the reaction system intermittently (i.e., in at least two different samples (aliquots)) together with the zinc precursor (e.g., to form the second semiconductor nanocrystals or the first particles). In the method of the embodiment, the sulfur precursor may be injected into the reaction system at once together with the zinc precursor, or may be divided into two or more doses.

[0141] The injection temperature can be suitably selected. The injection temperature can be greater than or equal to about 100°C, greater than or equal to about 150°C, greater than or equal to about 180°C, or greater than or equal to about 240°C and less than or equal to about the reaction temperature. The reaction conditions such as reaction temperature and reaction time for the formation of the second semiconductor nanocrystal can be suitably selected in consideration of the composition of the first semiconductor nanocrystal and the desired composition of the resulting semiconductor nanoparticles. The reaction temperature for the formation of the second semiconductor nanocrystal can be greater than or equal to about 240°C, greater than or equal to about 260°C, greater than or equal to about 280°C, or greater than or equal to about 300°C and less than or equal to about 380°C, less than or equal to about 350°C, or less than or equal to about 330°C.

[0142] The first particles obtained can be separated from the reaction system for the formation of the second semiconductor nanocrystal, and the separated first particles can be optionally washed with a washing solvent and then dispersed in a dispersion solvent (e.g., an alkane solvent such as hexane, octane, etc. or an aromatic hydrocarbon solvent). The first particles can be provided to the reaction system for forming the semiconductor nanocrystal layer optionally together with their dispersion solvent.

[0143] The reaction medium may include an organic solvent and optionally an organic ligand. The reaction medium may be pretreated under vacuum at a predetermined temperature. The pretreatment temperature may be greater than or equal to about 80°C, greater than or equal to about 90°C, greater than or equal to about 100°C, greater than or equal to about 120°C and less than or equal to about 180°C, or less than or equal to about 150°C. In an embodiment, prior to the pretreatment, the reaction system may include the zinc precursor.

[0144] The method may include adding the first particle and / or the sulfur precursor to a reaction medium including an organic solvent at a first temperature. The method may include adding a zinc precursor to the reaction medium (e.g., at the first temperature). Figure 1 .

[0145] The first temperature may be greater than or equal to about 180° C., greater than or equal to about 190° C., greater than or equal to about 200° C., greater than or equal to about 210° C., greater than or equal to about 220° C., greater than or equal to about 225° C., greater than or equal to about 230° C., greater than or equal to about 235° C., greater than or equal to about 240° C., or greater than or equal to about 280° C. The first temperature may be lower than a predetermined temperature or reaction temperature for formation of the semiconductor nanocrystal layer (hereinafter, referred to as a reaction temperature for ZnS formation). The first temperature may be less than or equal to about 320° C., less than or equal to about 319° C., less than or equal to about 310° C., less than or equal to about 305° C., less than or equal to about 300° C., less than or equal to about 290° C., less than or equal to about 280° C., less than or equal to about 270° C., less than or equal to about 260° C., or less than or equal to about 250° C.

[0146] The reaction temperature for forming the semiconductor nanocrystal layer (e.g., comprising ZnS) may be greater than or equal to about 325°C, greater than or equal to about 330°C, greater than or equal to about 331°C, greater than or equal to about 335°C, greater than or equal to about 336°C, greater than or equal to about 337°C, greater than or equal to about 338°C, greater than or equal to about 339°C, greater than or equal to about 340°C, greater than or equal to about 341°C, greater than or equal to about 342°C, greater than or equal to about 343°C, greater than or equal to about 344°C, or greater than or equal to about 345°C. The reaction temperature for ZnS formation may be (and may include temperatures of) about 300°C to about 390°C, about 319°C to about 380°C, about 320°C to about 375°C, about 325°C to about 370°C, about 330°C to about 360°C, about 335°C to about 360°C, about 336°C to about 360°C, about 340°C to about 355°C, about 345°C to about 355°C, about 350°C to about 355°C, or any combination of the low and high temperatures stated above.

[0147] Through their leading and extensive research on semiconductor nanoparticles, the present inventors have discovered that semiconductor nanoparticles including a semiconductor nanocrystal layer prepared using a thiol-based sulfur precursor may include a significant amount of thiol-derived ligands on the surface of the resulting nanoparticles, and this may adversely affect the performance of an electroluminescent device including the semiconductor nanoparticles.

[0148] Surprisingly, upon further investigation, the inventors discovered that by using a thiol-based sulfur precursor in the manner described herein under the reaction conditions described herein, for example, according to the method of the embodiments, improved quality can be achieved for the semiconductor nanocrystal layer (e.g., ZnS layer) formed therefrom, and unlike semiconductor nanoparticles prepared using known, e.g., conventional preparation methods, when the resulting semiconductor nanoparticles of the embodiments are included in an electroluminescent device, they can contribute to increased lifetime and improved electroluminescent properties in the device.

[0149] Surprisingly, according to the preparation method of the nanoparticle of embodiment, described semiconductor nano crystal layer can be formed with the coating rate that improves by using precursor described herein together with reaction conditions described herein.In addition, the semiconductor nanoparticles prepared thus can present controlled ligand composition.Do not wish to be bound by any theory, think, in the method for embodiment, reaction conditions together with the type of ligand composition can contribute to the interface or the defect at the surface that reduces in described semiconductor nanoparticle.

[0150] In the method of the embodiment, the sulfur precursor can present a more stable controlled (e.g., increased) reactivity in the reaction system, and under the reaction conditions described herein, the surface ligands of the resulting semiconductor nanoparticles can be controlled in a desired state, and thus the resulting light-emitting (e.g., electroluminescent) device including the semiconductor nanoparticles can present an improved lifespan together with improved luminous efficiency. It is believed that forming the semiconductor nanocrystal layer in the manner described herein can also lead to more control over the oxidation of the semiconductor nanoparticles, and this can provide a more uniformly formed shell, and thus, reduce surface defects of the nanoparticles.

[0151] In an embodiment, the sulfur precursor may include a compound represented by R-SH, wherein R is a C8-C50 (or C9-C45) substituted or unsubstituted aliphatic or aromatic hydrocarbon group (e.g., alkyl, alkenyl, alkynyl, phenyl, benzyl, etc.). The sulfur precursor may or may not include octyl mercaptan. In an embodiment, the sulfur precursor may include ethyl hexanethiol, decanethiol, undecyl mercaptan, dodecanethiol, tetradecanethiol, hexadecanethiol, octadecyl mercaptan, or a mixture thereof.

[0152] The sulfur precursor may or may not include a sulfur-hydrocarbon solvent adduct (e.g., a sulfur-hydrocarbon complex), which is prepared, for example, by dispersing or reacting sulfur in a hydrocarbon solvent. See below, the sulfur precursor may or may not include a bis(trialkylsilyl)alkyl sulfide (e.g., bis(trimethylsilyl)methyl sulfide), a bis(trialkylsilyl)sulfide (e.g., bis(trimethylsilyl)sulfide), or a combination thereof. In the method of the embodiment, in addition to the thiol-type precursor, an additional sulfur precursor (e.g., the aforementioned sulfur-hydrocarbon solvent adduct or the aforementioned thioether-based precursor) may be used, or the additional sulfur precursor may not be used.

[0153] The sulfur-hydrocarbon solvent adduct can be prepared by dispersing sulfur powder or elemental sulfur in a solvent containing a substituted or unsubstituted hydrocarbon group (e.g., an aliphatic hydrocarbon solvent such as octadecene, a phosphine solvent having an aliphatic or aromatic hydrocarbon group such as trioctylphosphine, diphenylphosphine, and triphenylphosphine, and an amine solvent having an aliphatic hydrocarbon group such as trioctylamine), and stirring it at a predetermined temperature. In an embodiment, the sulfur-hydrocarbon solvent adduct may include S-TOP, S-TOA, S-ODE, S-TBP, S-TPP, or a combination thereof. The preparation method of the sulfur-hydrocarbon solvent adduct is not particularly limited, and any known method may be used.

[0154] The amount of each precursor used in the method of the embodiment can be appropriately selected in consideration of the desired composition of the final semiconductor nanoparticles, the reactivity of the precursor, and the reaction conditions. In the method, each precursor (e.g., a zinc precursor, a sulfur precursor, or both) can be added once in a predetermined amount, or divided and injected at least twice, for example at least three times, and for example up to ten times, or five times.

[0155] In an embodiment, the first semiconductor nanocrystal includes a III-V compound including indium, phosphorus, and optionally zinc, and the amount of the zinc precursor used for the formation of the second semiconductor nanocrystal and the semiconductor nanocrystal layer may be greater than or equal to about 60 moles, greater than or equal to about 65 moles, greater than or equal to about 70 moles, greater than or equal to about 75 moles, greater than or equal to about 80 moles, or greater than or equal to about 85 moles, based on one mole of indium. The amount of the zinc precursor may be less than or equal to about 250 moles, less than or equal to about 200 moles, less than or equal to about 150 moles, less than or equal to about 100 moles, less than or equal to about 90 moles, or less than or equal to about 85 moles, based on one mole of indium.

[0156] In the method of the embodiment, the amount of the selenium precursor used for the formation of the second semiconductor nanocrystal may be, based on 1 mole of indium, greater than or equal to about 40 moles, greater than or equal to about 50 moles, greater than or equal to about 60 moles, greater than or equal to about 70 moles, greater than or equal to about 80 moles, or greater than or equal to about 90 moles. The amount of the selenium precursor may be, based on 1 mole of indium, less than or equal to about 200 moles, less than or equal to about 170 moles, less than or equal to about 150 moles, less than or equal to about 130 moles, less than or equal to about 110 moles, less than or equal to about 90 moles, less than or equal to about 80 moles, less than or equal to about 70 moles, less than or equal to about 60 moles, or less than or equal to about 55 moles.

[0157] In an embodiment, the first semiconductor nanocrystal includes a first zinc chalcogenide including zinc, selenium, and tellurium. In an embodiment, the amount of the selenium precursor used for the formation of the second semiconductor nanocrystal may be, based on 1 mole of zinc precursor, greater than or equal to about 0.1 mole, greater than or equal to about 0.3 mole, greater than or equal to about 0.5 mole, greater than or equal to about 0.65 mole, greater than or equal to about 0.7 mole, greater than or equal to about 0.9 mole, greater than or equal to about 1 mole, greater than or equal to about 1.5 mole, or greater than or equal to about 2 moles. Based on 1 mole of zinc precursor, the amount of the selenium precursor may be less than 5 moles, less than or equal to about 4 moles, less than or equal to about 3 moles, less than or equal to about 2 moles, or less than or equal to about 1 mole, but is not limited thereto.

[0158] With respect to the formation of the semiconductor nanocrystal layer, for example, the amount of the sulfur precursor can be determined by taking into account the type of precursor used, the reaction temperature, and the desired composition of the resulting nanoparticles. The amount of the sulfur precursor (the thiol compound, or the additional sulfur precursor (if any), or the total amount of the thiol compound and the additional sulfur precursor) (hereinafter referred to as the amount of the sulfur precursor) can be greater than or equal to about 0.05 mole, greater than or equal to about 0.1 mole, and less than or equal to about 10 moles, or less than or equal to 5 moles per mole of zinc in the zinc precursor. The amount of the sulfur precursor may be, based on 1 mole of zinc of the zinc precursor, about 0.08 mole or more, about 0.1 mole or more, about 0.15 mole or more, about 0.2 mole or more, about 0.25 mole or more, about 0.3 mole or more, about 0.5 mole or more, about 0.65 mole or more, about 0.7 mole or more, about 0.85 mole or more, about 0.9 mole or more, about 1 mole or more, about 1.2 mole or more, about 1.3 mole or more, or about 1.6 mole or more. mole, greater than or equal to about 1.5 moles, greater than or equal to about 1.8 moles, greater than or equal to about 2 moles, greater than or equal to about 2.5 moles, greater than or equal to about 3 moles, greater than or equal to about 3.5 moles, greater than or equal to about 4 moles, greater than or equal to about 4.5 moles, greater than or equal to about 5 moles, greater than or equal to about 5.5 moles, greater than or equal to about 6 moles, greater than or equal to about 6.5 moles, greater than or equal to about 7 moles, greater than or equal to about 7.5 moles, greater than or equal to about 8 moles, greater than or equal to about 8.5 moles, or greater than or equal to about 9 moles.

[0159] The amount of the sulfur precursor may be less than or equal to about 5 moles, less than or equal to about 3 moles, less than or equal to about 2.2 moles, or less than or equal to about 1.7 moles, based on 1 mole of zinc in the zinc precursor.

[0160] In the method of the embodiment, the zinc precursor may be Zn metal powder, ZnO, alkylated Zn compound (e.g., C2-C30 dialkyl zinc such as diethyl zinc), Zn alkoxide (e.g., zinc ethoxide), Zn carboxylate (e.g., zinc acetate), Zn nitrate, Zn perchlorate, Zn sulfate, Zn acetylacetonate, Zn halide (e.g., zinc chloride), Zn cyanide, Zn hydroxide, Zn carbonate, Zn peroxide, or a combination thereof. Examples of the zinc precursor may include dimethyl zinc, diethyl zinc, zinc acetate, zinc acetylacetonate, zinc iodide, zinc bromide, zinc chloride, zinc fluoride, zinc carbonate, zinc cyanide, zinc nitrate, zinc oxide, zinc peroxide, zinc perchlorate, zinc sulfate, or a combination thereof, but are not limited thereto.

[0161] In an embodiment, for the formation of the semiconductor nanocrystal layer, the zinc precursor may include a zinc carboxylate having a C1-C60 (or C5-C40) substituted or unsubstituted aliphatic hydrocarbon group. In an embodiment, for the formation of the semiconductor nanocrystal layer, the zinc precursor may include two or more different precursor compounds.

[0162] The zinc precursor may include a compound represented by Chemical Formula 1:

[0163] Chemical formula 1

[0164] ACOO-Zn-OOCB

[0165] In Chemical Formula 1, A and B are the same or different and are each independently a substituted or unsubstituted C1-C60 (straight or branched) aliphatic hydrocarbon (e.g., alkyl, alkenyl, or alkynyl) group, or a substituted or unsubstituted C3-C60 (or C6-C30) aromatic hydrocarbon group.

[0166] In Chemical Formula 1, A and B are the same or different and each independently may include a substituted or unsubstituted C1-C60, C12-C24, C16-C20, C4-C18, or C6-C8 straight-chain or branched aliphatic hydrocarbon group; a substituted or unsubstituted C3-C60 or C6-C30 aromatic hydrocarbon group (or aryl group) such as phenyl, benzyl or naphthyl; or a combination thereof.

[0167] In Chemical Formula 1, A and B may be the same or different, respectively, and may be ethylhexyl, methylbutyl, hexyldecyl, oleyl, myristyl, stearyl, aryl (eg, phenyl or benzyl), or a combination thereof.

[0168] The zinc precursor may include a zinc carboxylate having a C12-C60, C16-C24 or C18-C22 straight-chain aliphatic hydrocarbon group (i.e., a first zinc precursor), such as zinc oleate, zinc myristate, zinc stearate, etc.; a zinc carboxylate having a C3-C40, C4-C20, C4-C18 or C6-C8 branched aliphatic hydrocarbon group (i.e., a second zinc precursor), such as zinc ethylhexanoate (e.g., zinc 2-ethylhexanoate), zinc methylbutyrate (e.g., zinc 3-methylbutyrate), zinc hexyldecanoate (e.g., zinc 2-hexyldecanoate), etc.; or a combination thereof (e.g., a mixture thereof).

[0169] In an embodiment, a mixture of the zinc precursors may be used, and the molar ratio between the first and second zinc precursors may be suitably selected. In an embodiment, the molar ratio between the first zinc precursor and the second zinc precursor (first zinc precursor: second zinc precursor) may be from about 1:10 to about 10:1, from about 1:8 to about 8:1, from about 1:6 to about 6:1, from about 1:5 to about 5:1, from about 1:5.25 to about 5.25:1, from about 1:4 to about 4:1, from about 1:3 to about 3:1, from about 1:2 to about 2:1, or a combination thereof.

[0170] The selenium precursor may include selenium-trioctylphosphine ("Se-TOP"), selenium-tributylphosphine ("Se-TBP"), selenium-triphenylphosphine ("Se-TPP"), selenium-diphenylphosphine ("Se-DPP"), or a combination thereof, but is not limited thereto.

[0171] The tellurium precursor may include tellurium-tributylphosphine ("Te-TBP"), tellurium-triphenylphosphine ("Te-TPP"), tellurium-diphenylphosphine ("Te-DPP"), or a combination thereof, but is not limited thereto.

[0172] The sulfur precursor used in the preparation of the first or second semiconductor nanocrystal is not particularly limited and can be suitably selected. The sulfur precursor can be hexyl mercaptan, octyl mercaptan, decanethiol, dodecanethiol, hexadecyl mercaptan, mercaptopropyl silane, sulfur-trioctyl phosphine ("S-TOP"), sulfur-tributyl phosphine ("S-TBP"), sulfur-triphenylphosphine ("S-TPP"), sulfur-trioctylamine ("S-TOA"), bis (trialkylsilyl) sulfide, bis (trialkylsilyl alkyl) sulfide such as bis (trimethylsilylmethyl) sulfide, ammonium sulfide, sodium sulfide or its combination. In the formation of the semiconductor nanocrystal layer including zinc sulfide, the aforementioned sulfur precursor used in the preparation of the first semiconductor nanocrystal or the second semiconductor nanocrystal can be used in combination with the sulfur precursor based on mercaptan described herein.

[0173] The organic solvent may include a C6-C22 primary amine such as hexadecylamine or oleylamine, a C6-C22 secondary amine such as dioctylamine, a C6-C40 tertiary amine such as trioctylamine, a nitrogen-containing heterocyclic compound such as pyridine, a C6-C40 olefin such as octadecene, a C6-C40 aliphatic hydrocarbon such as hexadecane, octadecane, or squalane, an aromatic hydrocarbon substituted with a C6-C30 alkyl group such as phenyldodecane, phenyltetradecane, or phenylhexadecane, a primary, secondary or tertiary phosphine substituted with a C6-C22 alkyl group, such as at least one (e.g., 1, 2, or 3) C6-C22 alkyl group (e.g., trioctylphosphine), a phosphine oxide substituted with a C6-C22 alkyl group, such as at least one (e.g., 1, 2, or 3) C6-C22 alkyl group (e.g., trioctylphosphine oxide), a C12-C22 aromatic ether such as phenyl ether or benzyl ether, or a combination thereof.

[0174] The semiconductor nanoparticles may have organic ligands on their surfaces. The organic ligands may coordinate, for example, bind to the surface of the produced nanocrystals and may have an effect on the luminescence and electrical properties of the nanocrystals and / or may allow the nanocrystals to be effectively dispersed in an organic solvent. The organic ligands may include RCOOH, RNH 2 , R 2 NH, R 3 N, RSH, RH 2 PO, R 2 HPO, R 3 PO, RH 2 P.R 2 HP, R 3 P, ROH, RCOOR', RPO(OH) 2 , R 2 POOH, or a combination thereof, wherein R and R' are independently substituted or unsubstituted C1-C40 (eg, C3-C24) aliphatic hydrocarbon groups, substituted or unsubstituted C6-C40 (eg, C6-C24) aromatic hydrocarbon groups, or a combination thereof. One or more organic ligands may be used.

[0175] Examples of organic ligand compounds may include methyl mercaptan, ethyl mercaptan, propyl mercaptan, butyl mercaptan, pentyl mercaptan, hexyl mercaptan, octyl mercaptan, dodecanethiol, hexyl mercaptan, octyl mercaptan, benzyl mercaptan; methylamine, ethylamine, propylamine, butylamine, pentylamine, hexylamine, octylamine, decylamine, hexadecylamine, oleylamine, octadecylamine, dimethylamine, diethylamine, dipropylamine; formic acid, acetic acid, propionic acid, butyric acid, pentanoic acid, hexanoic acid, heptanoic acid, octanoic acid, decanoic acid, hexadecanoic acid, octadecanoic acid, oleic acid, benzoic acid, palmitic acid, or stearic acid; phosphines such as methyl Phosphine, ethylphosphine, propylphosphine, butylphosphine, pentylphosphine, tributylphosphine, or trioctylphosphine; phosphine oxide compounds such as methylphosphine oxide, ethylphosphine oxide, propylphosphine oxide, butylphosphine oxide, or trioctylphosphine oxide; diphenylphosphine or triphenylphosphine compounds, or their oxide compounds; C5-C20 alkylphosphonic acid; C5-C20 alkylphosphinic acid such as hexylphosphinic acid, octylphosphinic acid, decanephosphinic acid, tetradecanephosphinic acid, hexadecanephosphinic acid, octadecanephosphinic acid; phosphonic acid; etc., but not limited thereto. One or more organic ligand compounds can be used. In an embodiment, the organic ligand compound can be RCOOH and an amine (for example, RNH 2 , R 2 NH, R 3 N, or a combination thereof), wherein R is independently a substituted or unsubstituted C1-C40 (C3-C24) aliphatic hydrocarbon group or a substituted or unsubstituted C6-C40 (C6-C20) aromatic hydrocarbon group.

[0176] The organic ligand compound may include a carboxylic acid. The organic ligand or the carboxylic acid may include a combination of a straight-chain carboxylic acid (e.g., R1COOH, wherein R1 may include a C5-C40, C8-C20 straight-chain aliphatic hydrocarbon group) and a branched carboxylic acid (e.g., R2COOH, R2 is a C3-C40 or C5-C12 branched aliphatic hydrocarbon group). The number of carbon atoms of R1 may be greater than the number of carbon atoms of R2. The number of carbon atoms of R1 may be less than the number of carbon atoms of R2.

[0177] In the case of the formation of the first semiconductor nanocrystal, the second semiconductor nanocrystal, or a semiconductor nanocrystal layer, after the reaction is completed, a non-solvent can be added to the reaction product, and the nanoparticles or nanocrystals coordinated with the ligand compound, for example, can be separated. The non-solvent can be a polar solvent that is miscible with the solvent used in the core formation reaction, the shell formation reaction, or a combination thereof and that the produced nanocrystals cannot be dispersed therein. The non-solvent can be selected in consideration of the solvent used in the reaction, and can be, for example, acetone, ethanol, butanol, isopropanol, ethylene glycol, water, tetrahydrofuran ("THF"), dimethyl sulfoxide ("DMSO"), diethyl ether, formaldehyde, acetaldehyde, a solvent with a solubility parameter similar to the aforementioned non-solvent, or a combination thereof. Nanocrystal particles can be separated by centrifugation, sedimentation, chromatography, or distillation. If desired, the separated nanocrystals can be added to a washing solvent and washed. The washing solvent is not particularly limited and can have a solubility parameter similar to the solubility parameter of the ligand, and can include, for example, hexane, heptane, octane, chloroform, toluene, benzene, etc.

[0178] The semiconductor nanoparticles of the embodiments may not be dispersible in water, any of the non-solvents listed above, or a mixture thereof. The semiconductor nanoparticles of the embodiments may be water-insoluble.

[0179] The semiconductor nanoparticles of the embodiment may be dispersed in the aforementioned organic solvent. In an embodiment, the semiconductor nanoparticles may be dispersed in C6-C40 aliphatic hydrocarbons, C6-C40 aromatic hydrocarbons, or a mixture thereof.

[0180] In an embodiment, the semiconductor nanoparticles may include a first organic ligand and a second organic ligand, wherein the first organic ligand has a C12 or higher carboxylate moiety (carboxylic acid moiety) (e.g., derived from a zinc carboxylate such as zinc oleate, or in the form of RCOO), and the second organic ligand includes a thiol moiety (thiol moiety) (e.g., derived from a thiol compound, or in the form of R'-S), and as measured by GC-MS analysis, the peak area of ​​the second organic ligand may be less than or equal to about 17%, for example, less than or equal to about 16%, less than ... or equal to about 15%, less than or equal to about 14%, less than or equal to about 13%, less than or equal to about 12%, less than or equal to about 11%, less than or equal to about 10%, less than or equal to about 9%, less than or equal to about 8%, less than or equal to about 7.5%, less than or equal to about 7%, less than or equal to about 6.5%, less than or equal to about 6%, less than or equal to about 5.5%, less than or equal to about 5%, less than or equal to about 4.5%, less than or equal to about 4%, less than or equal to about 3.8%, less than or equal to about 3.5%, less than or equal to about 2.5%, less than or equal to about 2%, or less than or equal to about 1.5%. In the above RCOO or R'S, R and R' are the same or different and are each independently a hydrocarbon group that may correspond to the hydrocarbon groups defined herein with respect to the zinc precursor and the thiol compound.

[0181] When analyzing the organic ligands included in the semiconductor nanoparticles, gas chromatography (GC) can easily and reproducibly provide reliable results. Gas chromatography (GC) is an analytical technique that can be used to separate, identify and quantify each (individual) chemical component in a mixture. In GC, a gas can carry a given sample through a GC device. In an embodiment, the carrier gas or mobile phase is not particularly limited, and may include (e.g., high purity) helium, hydrogen or nitrogen. In an embodiment, a gas chromatography analysis device may include an injection port (e.g., a split / non-split (SSL) injection port), a column (e.g., a wall-coated open tube (WCOT) capillary column containing a thin layer of a dimethylpolysiloxane stationary phase), and a detector (e.g., a flame ionization detector, FID or mass spectrometry, MS), but is not limited thereto. Many gas chromatography analysis devices are commercially available, and considering the compound to be detected, measurements can be performed according to the user guide provided by each manufacturer. It is known that the measurement method associated with GC is used to determine the ligand composition on semiconductor nanoparticles, and can provide substantially the same results.

[0182] The area of ​​the peak attributable to the second organic ligand (i.e., the peak area of ​​the second organic ligand) may be greater than or equal to about 0.01%, greater than or equal to about 0.05%, greater than or equal to about 0.1%, greater than or equal to about 0.3%, greater than or equal to about 0.5%, greater than or equal to about 0.7%, or greater than or equal to about 1% of the total area of ​​the peaks of the first and second organic ligands.

[0183] Without wishing to be bound by any theory, according to the methods of the embodiments, the semiconductor nanoparticles may include additional ligands (eg, ligands derived from fatty acids such as oleic acid or C5-C20 or C8 carboxylic acids) along with limited amounts of ligands derived from thiols.

[0184] In an embodiment, the semiconductor nanoparticles may have a residual weight of greater than or equal to about 85 wt%, greater than or equal to about 85.5 wt%, greater than or equal to about 87 wt%, or greater than or equal to about 88 wt% and 99 wt% or less, as measured in thermogravimetric analysis. In an embodiment, the semiconductor nanoparticles may have an amount of organic matter of less than or equal to about 15 wt%, less than or equal to about 14.5 wt%, less than or equal to about 13.5 wt%, less than or equal to about 13 wt%, less than or equal to about 12.5 wt%, less than or equal to about 12 wt%, less than or equal to about 12 wt%, or less than or equal to about 11.5 wt% and greater than or equal to about 1 wt%, or greater than or equal to about 5 wt%, as measured in thermogravimetric analysis.

[0185] As measured by thermogravimetric analysis, the semiconductor nanoparticles may exhibit a first peak (or first peak temperature) at a temperature greater than or equal to about 200° C. and less than or equal to about 300° C., for example, greater than or equal to about 210° C. and less than or equal to about 280° C., in a derivative thermogravimetric curve plotting derivative weight versus temperature. The semiconductor nanoparticles may exhibit a second peak (or second peak temperature) greater than or equal to about 400° C. and less than or equal to about 500° C., for example, greater than or equal to about 410° C. and less than or equal to about 490° C. in the derivative thermogravimetric curve. The intensity of the second peak may be greater than or equal to about three times the intensity of the first peak, or it may be greater than or equal to about five times the intensity of the first peak.

[0186] In an embodiment, the semiconductor nanoparticle may have a core-shell structure having a core and a shell disposed on the core. The core may include the first semiconductor nanocrystal. The shell may include the semiconductor nanocrystal layer, and the semiconductor nanocrystal layer includes zinc sulfide. The shell may further include the second semiconductor nanocrystal or a layer (e.g., a first shell layer) containing the second semiconductor nanocrystal. The second semiconductor nanocrystal or a layer (i.e., the first shell layer) containing the second semiconductor nanocrystal may be located between the core (or the first semiconductor nanocrystal) and the semiconductor nanocrystal layer (e.g., the second shell layer). The semiconductor nanocrystal layer may constitute or be the outermost layer of the semiconductor nanoparticle of an embodiment.

[0187] The shell may have a multilayer shell structure, wherein adjacent layers (e.g., the first shell and the second shell) have different compositions. The shell (or each layer of the multilayer shell) may be a gradient alloy having a composition that changes in the radial direction of the semiconductor nanoparticle. In an embodiment, in the shell, or in the second semiconductor nanocrystal, the amount of sulfur may change toward the surface of the semiconductor nanoparticle. For example, in the second semiconductor nanocrystal, the amount of sulfur may have a concentration gradient that increases as it moves away from the core or the first semiconductor nanocrystal.

[0188] The size of the first semiconductor nanocrystal or the core may be adjusted in consideration of composition and peak wavelength of light emission.

[0189] In an embodiment, the size or average size (hereinafter, sometimes referred to as "size") of the core or the first semiconductor nanocrystal may be greater than or equal to about 1 nm, greater than or equal to about 1.5 nm, greater than or equal to about 1.9 nm, greater than or equal to about 2 nm, greater than or equal to about 2.1 nm, greater than or equal to about 2.3 nm, greater than or equal to about 2.5 nm, greater than or equal to about 3 nm, or greater than or equal to about 5 nm. The size of the core or the first semiconductor nanocrystal may be less than or equal to about 8 nm, less than or equal to about 6 nm, less than or equal to about 5 nm, less than or equal to about 4 nm, less than or equal to about 3.5 nm, less than or equal to about 3 nm, less than or equal to about 2.7 nm, or less than or equal to about 2.5 nm.

[0190] In an embodiment, the thickness or average thickness (hereinafter, "thickness") of the second semiconductor nanocrystal (e.g., zinc selenide, zinc selenide sulfide) or a layer including the same (i.e., the thickness of the first shell layer) may be greater than or equal to about 0.7 nm, greater than or equal to about 1 nm, greater than or equal to about 1.2 nm, greater than or equal to about 1.5 nm, greater than or equal to about 1.7 nm, greater than or equal to about 2.1 nm, greater than or equal to about 2.2 nm, greater than or equal to about 2.3 nm, greater than or equal to about 2.4 nm, greater than or equal to about 2.5 nm, greater than or equal to about 2.7 nm, greater than or equal to about 2.9 nm, greater than or equal to about 3 nm, greater than or equal to about 3.1 nm, greater than or equal to about 3.2 nm, greater than or equal to about 3.4 nm, greater than or equal to about 3.6 nm, greater than or equal to about 3.8 nm, or greater than or equal to about 4 nm. The thickness of the first shell layer may be less than or equal to about 6 nm, less than or equal to about 5.5 nm, less than or equal to about 5 nm, less than or equal to about 4.8 nm, less than or equal to about 4.5 nm, less than or equal to about 4 nm, less than or equal to about 3.5 nm, less than or equal to about 3 nm, less than or equal to about 2.5 nm, less than or equal to about 2.3 nm, less than or equal to about 2 nm, less than or equal to about 1.8 nm, less than or equal to about 1.5 nm, or less than or equal to about 1 nm.

[0191] In embodiments, the semiconductor nanocrystal layer may have a thickness of greater than or equal to about 0.1 nm, greater than or equal to about 0.2 nm, greater than or equal to about 0.25 nm, greater than or equal to about 0.3 nm, greater than or equal to about 0.45 nm, greater than or equal to about 0.5 nm, greater than or equal to about 0.7 nm, greater than or equal to about 0.9 nm, greater than or equal to about 1 nm, greater than or equal to about 1.1 nm, greater than or equal to about 1.3 nm, greater than or equal to about 1.5 nm, greater than or equal to about 1.7 nm, greater than or equal to about 1.9 nm, greater than or equal to about 2 nm, greater than or equal to about 2.1 nm, greater than or equal to about 2.3 nm, greater than or equal to about 2.5 nm, greater than or equal to about 2.7 nm, greater than or equal to about 2.9 nm, or greater than or equal to about 3 nm. The thickness of the semiconductor nanocrystal layer may be less than or equal to about 4 nm, less than or equal to about 3 nm, less than or equal to about 2 nm, less than or equal to about 1.5 nm, less than or equal to about 1 nm, less than or equal to about 0.7 nm, less than or equal to about 0.5 nm, less than or equal to about 0.45 nm, or less than or equal to about 0.32 nm.

[0192] The size or average size (referred to herein as “size”) of the semiconductor nanoparticles may be greater than or equal to about 7.3 nm, greater than or equal to about 7.4 nm, greater than or equal to about 7.5 nm, greater than or equal to about 7.6 nm, greater than or equal to about 7.7 nm, greater than or equal to about 7.8 nm, greater than or equal to about 7.9 nm, greater than or equal to about 8 nm, greater than or equal to about 8.5 nm, greater than or equal to about 9 nm, greater than or equal to about 9.5 nm, greater than or equal to about 10 nm, greater than or equal to about 10.5 nm, greater than or equal to about 11 nm, greater than or equal to about 11.5 nm, greater than or equal to about 12 nm, greater than or equal to about 12.5 nm, greater than or equal to about 13 nm, greater than or equal to about 13.5 nm, greater than or equal to about 14 nm, greater than or equal to about 14.5 nm, greater than or equal to about 15 nm, greater than or equal to about 15.5 nm, or greater than or equal to about 16 nm. The size of the semiconductor nanoparticles may be less than or equal to about 50 nm, less than or equal to about 45 nm, less than or equal to about 40 nm, less than or equal to about 35 nm, less than or equal to about 30 nm, less than or equal to about 25 nm, less than or equal to about 20 nm, less than or equal to about 15 nm, less than or equal to about 14 nm, less than or equal to about 13.5 nm, less than or equal to about 13 nm, less than or equal to about 11 nm, or less than or equal to about 10.2 nm.

[0193] The size of the semiconductor nanoparticles can be a diameter or an equivalent diameter calculated under the assumption of a sphere. The particle size of the semiconductor nanoparticles can be determined by an electron microscope image (e.g., a transmission electron microscopy image). As used herein, average can be a mean average. As used herein, average can be a median.

[0194] In the semiconductor nanoparticles of the embodiment, the standard deviation of the particle size may be in the range of about 1% to about 20%, about 2% to about 19%, about 3% to about 18%, about 4% to about 17%, about 5% to about 16%, about 6% to about 14%, about 7% to about 13%, about 8% to about 12%, about 9% to about 11%, or a combination thereof. The semiconductor nanoparticles of the embodiment may have a standard deviation of 10% or less, 9% or less, 8% or less, 7% or less, 6% or less, or 5% or less of the average size.

[0195] In an embodiment, the particle size can be easily and reproducibly analyzed and obtained by using an image (two-dimensional image) obtained by electron microscopy analysis (e.g., transmission electron microscopy analysis or scanning electron microscopy analysis) and using any suitable (known or commercially available) image analysis program such as "Image J" or in-house or commercially available software (e.g., software made using a programming language such as phython), for example, according to a manual provided by the manufacturer. Image analysis tools and measurement conditions are not particularly limited.

[0196] Semiconductor nanoparticles according to embodiments may have a relatively reduced level of circularity. Circularity is a shape factor of how close a cross section of a given particle is to a circle in consideration of the smoothness of the circumference (perimeter).

[0197] Circularity can be determined in two-dimensional images obtained by electron microscopy analysis by the following definition:

[0198]

[0199] Wherein "area" is the area of ​​the two-dimensional image of a separate (individual) semiconductor nanoparticle, and "perimeter" is the perimeter of the two-dimensional image of a separate semiconductor nanoparticle.

[0200] In embodiments, the semiconductor nanoparticles may have a roundness or average roundness (referred to herein as "roundness") of greater than or equal to about 0.77, greater than or equal to about 0.8, greater than or equal to about 0.82, greater than or equal to about 0.83, or greater than or equal to about 0.85 and less than or equal to about 1, less than or equal to about 0.9, less than or equal to about 0.87, less than or equal to about 0.86, less than or equal to about 0.85, or less than or equal to about 0.84.

[0201] In embodiments, the semiconductor nanoparticles may have a roundness or average roundness (hereinafter, "roundness") of greater than or equal to about 0.65, greater than or equal to about 0.7, greater than or equal to about 0.71, greater than or equal to about 0.72, greater than or equal to about 0.74, greater than or equal to about 0.75 and less than or equal to about 1, less than or equal to about 0.9, less than or equal to about 0.85, less than or equal to about 0.8, less than or equal to about 0.79, or less than or equal to about 0.78.

[0202] Circularity is defined by the following equation:

[0203]

[0204] Area: The area of ​​the 2D image of an individual semiconductor nanoparticle.

[0205] Major axis: The longest diameter of a semiconductor nanoparticle.

[0206] Semiconductor nanoparticles according to one embodiment may exhibit an enhanced level of solidity. Solidity S is defined by the following equation as the image area A divided by the convex hull area Ac.

[0207]

[0208] A: Area of ​​the 2D image of a single semiconductor nanoparticle

[0209] Ac: The area of ​​the convex hull of the two-dimensional image of a single semiconductor nanoparticle

[0210] The semiconductor nanoparticles may exhibit a relatively high solidity. In embodiments, the semiconductor nanoparticles or a population thereof may have a solidity or average solidity (referred to herein as "solidity") of greater than or equal to about 0.97, greater than or equal to about 0.975, or greater than or equal to about 0.98.

[0211] The shape factor (e.g., roundness or solidity) can be easily and reproducibly obtained from two-dimensional electron microscopy images of particles using a general analysis program (e.g., Image J developed by NIH) and the program manufacturer's manual (e.g., Image J User Guide IJ 1.46r) or an in-house imaging program made by a coding language (e.g., a commercially available coding language such as Matlab).

[0212] In an embodiment, the semiconductor nanoparticles, the light-emitting layer including the semiconductor nanoparticles, or the light-emitting device including the semiconductor nanoparticles (e.g., an electroluminescent device) may be configured to emit blue light, green light, or red light. In an embodiment, the semiconductor nanoparticles, the light-emitting layer including the semiconductor nanoparticles, or the light-emitting device may emit blue light, for example, by light excitation (i.e., when the light-emitting layer is irradiated with light) or by applying a voltage. In an embodiment, the semiconductor nanoparticles, the light-emitting layer, or the light-emitting device may emit green light, for example, by light excitation (e.g., when irradiated with light) or by applying a voltage. In an embodiment, the semiconductor nanoparticles, the light-emitting layer, or the light-emitting device may emit red light, for example, by light excitation (e.g., when irradiated with light) or by applying a voltage.

[0213] The peak emission wavelength of the blue light may be greater than or equal to about 430 nm, greater than or equal to about 435 nm, greater than or equal to about 440 nm, greater than or equal to about 446 nm, greater than or equal to about 449 nm, greater than or equal to about 450 nm, greater than or equal to about 455 nm, greater than or equal to about 460 nm, greater than or equal to about 465 nm, greater than or equal to about 470 nm, greater than or equal to about 477 nm and less than about 480 nm (e.g., less than or equal to about 470 nm, less than or equal to about 465 nm, less than or equal to about 460 nm, or less than or equal to about 455 nm). The peak emission wavelength of the blue light may be greater than or equal to about 453 nm, greater than or equal to about 455 nm, greater than or equal to about 458 nm, greater than or equal to about 460 nm, greater than or equal to about 465 nm, greater than or equal to about 466 nm, greater than or equal to about 468 nm, or greater than or equal to about 470 nm. The peak emission wavelength of the blue light may be less than or equal to about 475 nm, less than or equal to about 473 nm, less than or equal to about 472 nm, or less than or equal to about 470 nm.

[0214] The peak emission wavelength of the green light may be greater than or equal to about 480 nm, for example, greater than or equal to about 490 nm, greater than or equal to about 500 nm, greater than or equal to about 510 nm, greater than or equal to about 515 nm, greater than or equal to about 520 nm, greater than or equal to about 525 nm, greater than or equal to about 530 nm, greater than or equal to about 535 nm, or greater than or equal to about 540 nm and less than or equal to about 580 nm, less than or equal to about 570 nm, less than or equal to about 565 nm, less than or equal to about 560 nm, less than or equal to about 555 nm, less than or equal to about 550 nm, or less than or equal to about 545 nm.

[0215] The peak emission wavelength of the red light may be greater than or equal to about 600 nm and less than or equal to about 650 nm.

[0216] The semiconductor nanoparticles of the embodiment may exhibit improved luminous efficiency. The semiconductor nanoparticles may exhibit a quantum yield (e.g., absolute quantum yield, herein, referred to as "quantum yield") greater than or equal to about 90%, greater than or equal to about 91%, greater than or equal to about 92%, greater than or equal to about 93%, greater than or equal to about 94%, greater than or equal to about 95%, greater than or equal to about 96%, greater than or equal to about 97%, greater than or equal to about 98%, or greater than or equal to about 99%. The quantum yield may be from about 75% to about 100%, from about 80% to about 99%, from 85% to about 98%, from about 90% to about 95%, or a combination thereof. In an embodiment, the semiconductor nanoparticles may have a quantum yield greater than or equal to about 65%. In embodiments, the semiconductor nanoparticles may have a quantum yield of greater than or equal to about 65%, greater than or equal to about 70%, greater than or equal to about 75%, greater than or equal to about 80%, greater than or equal to about 85%, or greater than or equal to about 88%.

[0217] The semiconductor nanoparticles or the light-emitting layer including the semiconductor nanoparticles may exhibit a half width (e.g., a luminescence peak) of less than or equal to about 50 nm. The half width may be less than or equal to about 45 nm, less than or equal to about 44 nm, less than or equal to about 43 nm, less than or equal to about 42 nm, less than or equal to about 41 nm, less than or equal to about 40 nm, less than or equal to about 39 nm, less than or equal to about 38 nm, less than or equal to about 37 nm, less than or equal to about 36 nm, less than or equal to about 35 nm, less than or equal to about 34 nm, or less than or equal to about 33 nm. The half width may be greater than or equal to about 2 nm, greater than or equal to about 5 nm, greater than or equal to about 10 nm, greater than or equal to about 12 nm, or greater than or equal to about 15 nm.

[0218] Here, the optical properties of the semiconductor nanoparticles (eg, photoluminescence quantum yield PLQY, UV absorption properties, half width FWHM, etc.) are measured at room temperature, for example, at a temperature of 20° C. to 25° C., unless otherwise specified.

[0219] In an embodiment, the semiconductor nanoparticles include zinc, selenium, tellurium, and sulfur, and do not include cadmium, the semiconductor nanoparticles are configured to emit blue light, the semiconductor nanoparticles have an absolute quantum yield greater than or equal to about 90%, or greater than or equal to about 95%, and the molar ratio of zinc to selenium may be greater than or equal to about 1:1, or greater than or equal to about 1.5:1 and less than or equal to about 3:1, less than or equal to about 2.5:1, or less than or equal to about 2.3:1. In the semiconductor nanoparticles, the molar ratio of sulfur to tellurium (S:Te) may be greater than or equal to about 10:1, or greater than or equal to about 50:1 and less than or equal to about 180:1, or less than or equal to about 120:1. The semiconductor nanoparticles may include the semiconductor nanocrystal layer. The semiconductor nanoparticles may exhibit the structure and / or properties described herein. The blue light may have a peak wavelength greater than or equal to about 440 nm, or greater than or equal to about 450 nm and less than about 480 nm, or less than or equal to about 479 nm.

[0220] The semiconductor nanoparticles of the embodiment may include the first semiconductor nanocrystal. The first semiconductor nanocrystal may include ZnTe x Se 1-x (where x is greater than 0, greater than or equal to about 0.001, greater than or equal to about 0.003, greater than or equal to about 0.005, greater than or equal to about 0.007, greater than or equal to about 0.009, greater than or equal to about 0.01, greater than or equal to about 0.03, greater than or equal to about 0.05, greater than or equal to about 0.09 and less than 0.1, or less than or equal to about 0.04.) The core may or may not include sulfur.

[0221] In the semiconductor nanoparticles or the light-emitting layer including the semiconductor nanoparticles, the molar ratio of zinc to selenium (Zn:Se) may be greater than or equal to about 1.1:1, greater than or equal to about 1.2:1, greater than or equal to about 1.3:1, greater than or equal to about 1.4:1, greater than or equal to about 1.5:1, greater than or equal to about 1.6:1, greater than or equal to about 1.7:1, greater than or equal to about 1.8:1, or greater than or equal to about 1.9:1. The molar ratio of zinc to selenium (Zn / Se) may be less than or equal to about 2.8:1, less than or equal to about 2.4:1, less than or equal to about 2.3:1, less than or equal to about 2.25:1, less than or equal to about 2.2:1, less than or equal to about 2.1:1, less than or equal to about 2:1, less than or equal to about 1.95:1, less than or equal to about 1.93:1, less than or equal to about 1.91:1, less than or equal to about 1.9:1, less than or equal to about 1.89:1, less than or equal to about 1.87:1, less than or equal to about 1.85:1, less than or equal to about 1.84:1, less than or equal to about 1.81:1, less than or equal to about 1.8:1, less than or equal to about 1.79:1, less than or equal to about 1.77:1, or less than or equal to about 1.75:1.

[0222] In the semiconductor nanoparticle or the light-emitting layer including the semiconductor nanoparticle, the molar ratio of sulfur to tellurium (S:Te) may be greater than or equal to about 15:1, greater than or equal to about 20:1, greater than or equal to about 25:1, greater than or equal to about 30:1, greater than or equal to about 35:1, greater than or equal to about 40:1, greater than or equal to about 45:1, greater than or equal to about 50:1, greater than or equal to about 55:1, greater than or equal to about 60:1, greater than or equal to about 65:1, greater than or equal to about 70:1, greater than or equal to about 71:1, greater than or equal to about 72:1, greater than or equal to about 73:1, greater than or equal to about 74:1, greater than or equal to about 76:1, greater than or equal to about 77:1, greater than or equal to about 78:1, greater than or equal to about 79:1, greater than or equal to about 80:1, greater than or equal to about 81:1, greater than or equal to about 82:1, greater than or equal to about 83:1, greater than or equal to about 84:1, greater than or equal to about 86:1, greater than or equal to about 87:1, greater than or equal to about 88:1, greater than or equal to about 89:1, greater than or equal to about 90:1, greater than or equal to about 91:1, greater than or equal to about 92:1, greater than or equal to about 93:1, greater than or equal to about 94:1 or equal to about 73:1, greater than or equal to about 74:1, greater than or equal to about 75:1, greater than or equal to about 77:1, greater than or equal to about 79:1, greater than or equal to about 80:1, greater than or equal to about 82:1, greater than or equal to about 84:1, greater than or equal to about 86:1, greater than or equal to about 88:1, greater than or equal to about 89:1, greater than or equal to about 90:1, greater than or equal to about 93:1, greater than or equal to about 95:1, greater than or equal to about 97:1, greater than or equal to about 99:1, or greater than or equal to about 100:1. In the semiconductor nanoparticles or the light-emitting layer including the semiconductor nanoparticles, the molar ratio of sulfur to tellurium (S:Te) may be less than or equal to about 180:1, less than or equal to about 175:1, less than or equal to about 170:1, less than or equal to about 165:1, less than or equal to about 160:1, less than or equal to about 155:1, less than or equal to about 150:1, less than or equal to about 145:1, less than or equal to about 140:1, less than or equal to about 135:1, less than or equal to about 130:1, less than or equal to about 125:1, less than or equal to about 120:1, less than or equal to about 115:1, less than or equal to about 150:1, less than or equal to about 145:1, less than or equal to about 140:1, less than or equal to about 135:1, less than or equal to about 130:1, less than or equal to about 125:1, less than or equal to about 120:1, less than or equal to about 115:1, less than or equal to about less than or equal to about 104:1, less than or equal to about 103:1, less than or equal to about 102:1, less than or equal to about 101:1, less than or equal to about 100:1, less than or equal to about 99:1, less than or equal to about 98:1, less than or equal to about 97:1, less than or equal to about 96:1, less than or equal to about 95:1, less than or equal to about 93:1, less than or equal to about 92:1, or less than or equal to about 91:1.

[0223] In the semiconductor nanoparticles or the light-emitting layer including the semiconductor nanoparticles, the molar ratio of tellurium to selenium (Te:Se) may be less than or equal to about 0.1:1, less than or equal to about 0.08:1, less than or equal to about 0.07:1, less than or equal to about 0.06:1, less than or equal to about 0.05:1, less than or equal to about 0.045:1, less than or equal to about 0.04:1, less than or equal to about 0.035:1, less than or equal to about 0.03:1, less than or equal to about 0.025:1, less than or equal to about 0.02:1, less than or equal to about 0.015:1, less than or equal to about 0.01:1, less than or equal to about 0.009:1, less than or equal to about 0.008:1, less than or equal to about 0.007:1, less than or equal to about 0.006:1, or less than or equal to about 0.005:1. The molar ratio of tellurium to selenium (Te:Se) may be greater than or equal to about 0.0001:1, greater than or equal to about 0.00015:1, greater than or equal to about 0.0002:1, greater than or equal to about 0.00025:1, greater than or equal to about 0.0003:1, greater than or equal to about 0.00035:1, greater than or equal to about 0.0004:1, greater than or equal to about 0.00045:1, greater than or equal to about 0.0005:1, greater than or equal to about 0.00055:1, greater than or equal to about 0.0006:1, greater than or equal to about 0.00065:1, greater than or equal to about In the semiconductor nanoparticles of the embodiment, the molar ratio of tellurium to selenium (Te:Se) may be from about 0.004:1 to about 0.01:1. The molar ratio of tellurium to selenium (Te:Se) may be about 0.0002:1 to about 0.02:1. The molar ratio of tellurium to selenium (Te:Se) may be about 0.0003:1 to about 0.03:1.

[0224] In the semiconductor nanoparticles or the light-emitting layer including the semiconductor nanoparticles, the molar ratio of tellurium to zinc (Te:Zn) may be less than or equal to about 0.02:1, less than or equal to about 0.015:1, less than or equal to about 0.01:1, less than or equal to about 0.009:1, less than or equal to about 0.008:1, less than or equal to about 0.007:1, less than or equal to about 0.006:1, or less than or equal to about 0.005:1. The molar ratio of tellurium to zinc (Te:Zn) may be greater than or equal to about 0.0001:1, greater than or equal to about 0.0005:1, greater than or equal to about 0.001:1, greater than or equal to about 0.0015:1, greater than or equal to about 0.002:1, greater than or equal to about 0.0025:1, greater than or equal to about 0.003:1, greater than or equal to about 0.0035:1, or greater than or equal to about 0.004:1.

[0225] In the semiconductor nanoparticles or the light-emitting layer including the semiconductor nanoparticles, the molar ratio of Se to Zn (Se:Zn) may be less than or equal to about 1:1, for example, less than or equal to about 0.95:1, less than or equal to about 0.90:1, less than or equal to about 0.85:1, less than or equal to about 0.8:1, less than or equal to about 0.7:1, less than or equal to about 0.6:1, less than or equal to about 0.55:1, less than or equal to about 0.5:1, less than or equal to about 0.45:1, or less than or equal to about 0.4:1. The molar ratio of Se to Zn (Se:Zn) may be greater than or equal to about 0.1:1, greater than or equal to about 0.2:1, greater than or equal to about 0.3:1, greater than or equal to about 0.4:1, greater than or equal to about 0.45:1, greater than or equal to about 0.46:1, greater than or equal to about 0.48:1, greater than or equal to about 0.5:1, greater than or equal to about 0.52:1, greater than or equal to about 0.53:1, greater than or equal to about 0.54:1, greater than or equal to about 0.55:1, greater than or equal to about 0.56:1, greater than or equal to about 0.57:1, greater than or equal to about 0.58:1, greater than or equal to about 0.59:1, or greater than or equal to about 0.6:1.

[0226] In the semiconductor nanoparticles or the light-emitting layer including the semiconductor nanoparticles, the molar ratio of Se+S to zinc [(S+Se):Zn] may be greater than or equal to about 0.5:1, greater than or equal to about 0.6:1, greater than or equal to about 0.7:1, greater than or equal to about 0.8:1, greater than or equal to about 0.85:1, greater than or equal to about 0.88:1, greater than or equal to about 0.89:1, greater than or equal to about 0.9:1, greater than or equal to about 0.91:1, greater than or equal to about 0.92:1, greater than or equal to about 0.93:1, greater than or equal to about 0.94:1, greater than or equal to about 0.95:1, greater than or equal to about 0.96:1, greater than or equal to about 0.97:1, greater than or equal to about 0.98:1, greater than or equal to about 0.99:1, or greater than or equal to about 1:1. In the semiconductor nanoparticles or the light-emitting layer including the semiconductor nanoparticles, the molar ratio of Se+S to zinc [(S+Se):Zn] may be less than or equal to about 3:1, less than or equal to about 2.5:1, less than or equal to about 2:1, less than or equal to about 1.5:1, or less than or equal to about 1.2:1.

[0227] In the semiconductor nanoparticles or the light-emitting layer including the semiconductor nanoparticles, the molar ratio of sulfur to selenium (S:Se) may be less than or equal to about 1.5:1, less than or equal to about 1:1, less than or equal to about 0.9:1, less than or equal to about 0.8:1, less than or equal to about 0.79:1, less than or equal to about 0.78:1, less than or equal to about 0.73:1, less than or equal to about 0.7:1, less than or equal to about 0.696:1, less than or equal to about 0.69:1, less than or equal to about 0.67:1, less than or equal to about 0.63:1, less than or equal to about 0.62:1, or less than or equal to about 0.61:1. In an embodiment, in the semiconductor nanoparticles or the light-emitting layer including the semiconductor nanoparticles, the molar ratio of sulfur to selenium (S:Se) may be greater than or equal to about 0.3:1, greater than or equal to about 0.35:1, greater than or equal to about 0.4:1, greater than or equal to about 0.45:1, greater than or equal to about 0.5:1, greater than or equal to about 0.55:1, greater than or equal to about 0.6:1, greater than or equal to about 0.61:1, greater than or equal to about 0.64:1, greater than or equal to about 0.65:1, greater than or equal to about 0.67:1, greater than or equal to about 0.68:1, greater than or equal to about 0.69:1, greater than or equal to about 0.7:1, greater than or equal to about 0.74:1, or greater than or equal to about 0.76:1.

[0228] In the semiconductor nanoparticles or the light-emitting layer including the semiconductor nanoparticles, the molar ratio of sulfur to the sum of selenium and sulfur [S:(S+Se)] may be greater than or equal to about 0.29:1, greater than or equal to about 0.31:1, greater than or equal to about 0.32:1, greater than or equal to about 0.33:1, greater than or equal to about 0.34:1, greater than or equal to about 0.35:1, greater than or equal to about 0.36:1, greater than or equal to about 0.37:1, greater than or equal to about 0.38:1, greater than or equal to about 0.39:1, greater than or equal to about 0.40:1, greater than or equal to about 0.41:1, greater than or equal to about 0.42:1, or greater than or equal to about 0.43:1. The molar ratio of sulfur to the sum of selenium and sulfur [S:(S+Se)] may be less than or equal to about 0.53:1, less than or equal to about 0.52:1, less than or equal to about 0.51:1, less than or equal to about 0.5:1, less than or equal to about 0.49:1, less than or equal to about 0.48:1, less than or equal to about 0.47:1, less than or equal to about 0.46:1, less than or equal to about 0.45:1, less than or equal to about 0.44:1, or less than or equal to about 0.43:1.

[0229] The molar amount of an element as described herein (e.g., included in the semiconductor nanoparticles or the light-emitting layer) or the molar ratio between the elements can be determined, for example, using a suitable analytical tool (e.g., inductively coupled plasma atomic emission spectroscopy (ICP-AES), X-ray photoelectron spectroscopy (XPS), ion chromatography, transmission electron microscopy-energy dispersive X-ray spectroscopy (TEM-EDX), scanning electron microscopy-energy dispersive X-ray spectroscopy (SEM-EDX), X-ray fluorescence (XRF), or a combination thereof).

[0230] In an embodiment, the semiconductor nanoparticles include indium, phosphorus, zinc, selenium, and sulfur, and the semiconductor nanoparticles include a semiconductor nanocrystal layer including zinc sulfide, and the semiconductor nanoparticles can be configured to emit green light. The semiconductor nanoparticles do not include cadmium. The semiconductor nanoparticles can have the structure and properties described herein.

[0231] In the semiconductor nanoparticles or the light-emitting layer including the semiconductor nanoparticles, the molar ratio of zinc to indium (Zn:In) may be greater than or equal to about 39:1, greater than or equal to about 40:1, greater than or equal to about 41:1, greater than or equal to about 42:1, greater than or equal to about 43:1, greater than or equal to about 44:1, greater than or equal to about 45:1, greater than or equal to about 46:1, greater than or equal to about 47:1, greater than or equal to about 48:1, greater than or equal to about 49:1, greater than or equal to about 50:1, greater than or equal to about 51:1, greater than or equal to about 52:1, greater than or equal to about 53:1, greater than or equal to about 54:1, greater than or equal to about 56:1, greater than or equal to about 57:1, greater than or equal to about 58:1, greater than or equal to about 59:1, greater than or equal to about 60:1, greater than or equal to about 61:1, greater than or equal to about 62:1, greater than or equal to about 64:1, greater than or equal to about 65:1, greater than or equal to about 66:1, greater than or equal to about 67:1, greater than or equal to about 68:1, greater than or equal to about 69:1, greater than or equal to about 70:1, greater than or equal to about 71:1, greater than or equal to about greater than or equal to about 51:1, greater than or equal to about 52:1, greater than or equal to about 53:1, greater than or equal to about 54:1, greater than or equal to about 55:1, greater than or equal to about 56:1, greater than or equal to about 57:1, greater than or equal to about 58:1, greater than or equal to about 59:1, greater than or equal to about 60:1, greater than or equal to about 61:1, greater than or equal to about 62:1, greater than or equal to about 63:1, greater than or equal to about 64:1, greater than or equal to about 65:1, or greater than or equal to about 66:1. In the semiconductor nanoparticles or the light-emitting layer including the semiconductor nanoparticles, the molar ratio of zinc to indium (Zn:In) may be greater than or equal to about 60:1, greater than or equal to about 67:1, greater than or equal to about 68:1, greater than or equal to about 69:1, greater than or equal to about 70:1, greater than or equal to about 71:1, greater than or equal to about 72:1, greater than or equal to about 73:1, greater than or equal to about 74:1, greater than or equal to about 75:1, greater than or equal to about 76:1, greater than or equal to about 77:1, greater than or equal to about 78:1, greater than or equal to about 79:1, or greater than or equal to about 80:1.

[0232] The molar ratio of zinc to indium may be less than or equal to about 250:1, less than or equal to about 240:1, less than or equal to about 230:1, less than or equal to about 220:1, less than or equal to about 210:1, less than or equal to about 200:1, less than or equal to about 190:1, less than or equal to about 180:1, less than or equal to about 170:1, less than or equal to about 160:1, less than or equal to about 150:1, less than or equal to about 140:1, less than or equal to about 130:1, less than or equal to about 120:1, less than or equal to about 110:1, less than or equal to about 105:1, less than or equal to about 100:1, less than or equal to about 1 less than or equal to about 64:1, less than or equal to about 63:1, less than or equal to about 62:1, less than or equal to about 61:1, less than or equal to about 60:1, or less than or equal to about 59:1. In embodiments, the molar ratio of zinc to indium may be from about 60:1 to about 250:1, from about 67:1 to about 230:1, from about 70:1 to about 200:1, from about 75:1 to about 150:1, from about 77:1 to about 130:1, from about 80:1 to about 125:1, from about 90:1 to about 110:1, from about 95:1 to about 107:1, from about 100:1 to about 105:1, or combinations thereof.

[0233] In an embodiment, in the semiconductor nanoparticles or the light-emitting layer including the semiconductor nanoparticles, the molar ratio of selenium to indium (Se:In) may be greater than or equal to about 25:1, greater than or equal to about 29:1, greater than or equal to about 30:1, greater than or equal to about 35:1, greater than or equal to about 37:1, greater than or equal to about 38:1, greater than or equal to about 39:1, greater than or equal to about 40:1, greater than or equal to about 41:1, greater than or equal to about 42:1, greater than or equal to about 43:1, greater than or equal to about 44:1, greater than or equal to about 45:1, greater than or equal to about 46:1, greater than or equal to about 47:1, greater than or equal to about 48:1, greater than or equal to about 49:1, greater than or equal to about 50:1, greater than or equal to about 51:1, greater than or equal to about 52:1, greater than or equal to about 53:1, greater than or equal to about 54:1, greater than or equal to about 55:1, greater than or equal to about 56:1, greater than or equal to about 57:1, greater than or equal to about 58:1, greater than or equal to about 59:1, greater than or equal to about 60:1, greater than or equal to about 61:1, greater than or equal to about 62:1, greater than or equal to about 63:1, greater than or equal to about 64:1, greater than or equal to about 65:1, greater than or equal to about 66:1, greater than or equal to about 67:1, greater than or equal to about equal to about 45:1, greater than or equal to about 46:1, greater than or equal to about 47:1, greater than or equal to about 48:1, greater than or equal to about 49:1, greater than or equal to about 50:1, greater than or equal to about 51 :1, greater than or equal to about 53:1, greater than or equal to about 57:1, greater than or equal to about 59:1, greater than or equal to about 60:1, greater than or equal to about 61 :1, greater than or equal to about 63:1, greater than or equal to about 65:1, greater than or equal to about 67:1, greater than or equal to about 69:1, or greater than or equal to about 70:1. The molar ratio of selenium to indium may be less than or equal to about 200:1, less than or equal to about 180:1, less than or equal to about 170:1, less than or equal to about 160:1, less than or equal to about 150:1, less than or equal to about 140:1, less than or equal to about 130:1, less than or equal to about 120:1, less than or equal to about 110:1, less than or equal to about 100:1, less than or equal to about 90:1, less than or equal to about 80:1, less than or equal to about 75:1, less than or equal to about 74:1, less than or equal to about 73:1, less than or equal to about 72:1, less than or equal to about 71:1, less than or equal to about 72:1, less than or equal to about 73:1, less than or equal to about 74:1, less than or equal to about 75:1, less than or equal to about 76:1, less than or equal to about 77:1, less than or equal to about 78:1, less than or equal to about 79:1, less than or equal to about 80:1, less than or equal to about 81:1, less than or equal to about 82:1, less than or equal to about 83:1, less than or equal to about 84:1, less than or equal to about 85:1, less than or equal to about 86:1, less than or equal to about 87:1, less than or equal to about 88:1, less than or equal to about 89:1, less than or equal to about 90:1, less than or equal to about 91:1, less than or equal to about 92:1, less than or equal to about 93:1, less than or equal to about 94:1, less than or equal to about 9 equal to about 70:1, less than or equal to about 69:1, less than or equal to about 68:1, less than or equal to about 67:1, less than or equal to about 66:1, less than or equal to about 65:1, less than or equal to about 64:1, less than or equal to about 63:1, less than or equal to about 62:1, less than or equal to about 61:1, less than or equal to about 60:1, less than or equal to about 59:1, less than or equal to about 58:1, less than or equal to about 57:1, less than or equal to about 56:1, less than or equal to about 55:1, less than or equal to about 54:1, less than or equal to about 53:1, or less than or equal to about 52:1.

[0234] In an embodiment, in the semiconductor nanoparticles or the light-emitting layer including the semiconductor nanoparticles, the molar ratio of sulfur to indium (S:In) may be greater than or equal to about 11.2:1, greater than or equal to about 11.5:1, greater than or equal to about 12:1, greater than or equal to about 13:1, greater than or equal to about 14:1, greater than or equal to about 15:1, greater than or equal to about 16:1, greater than or equal to about 17:1, greater than or equal to about 18:1, greater than or equal to about 19:1, greater than or equal to about 20:1, greater than or equal to about 21:1, greater than or equal to about 22:1, greater than or equal to about 23:1, greater than or equal to about 24:1, or greater than or equal to about 25:1. The molar ratio of sulfur to indium (S:In) may be less than or equal to about 50:1, less than or equal to about 45:1, less than or equal to about 40:1, less than or equal to about 35:1, less than or equal to about 30:1, less than or equal to about 25:1, less than or equal to about 20:1, less than or equal to about 19:1, less than or equal to about 18:1, less than or equal to about 17:1, less than or equal to about 16:1, less than or equal to about 15:1, or less than or equal to about 14:1.

[0235] In an embodiment, in the semiconductor nanoparticle or the light-emitting layer including the semiconductor nanoparticle, the molar ratio of the sum of sulfur and selenium to indium [(S+Se):In] may be greater than or equal to about 50:1, greater than or equal to about 55:1, greater than or equal to about 60:1, greater than or equal to about 61:1, greater than or equal to about 63:1, greater than or equal to about 65:1, greater than or equal to about 67:1, greater than or equal to about 69:1, greater than or equal to about 70:1, greater than or equal to about 71:1, greater than or equal to about 72:1, greater than or equal to about 73:1, greater than or equal to about 74:1, greater than or equal to about 76:1, greater than or equal to about 77:1, greater than or equal to about 78:1, greater than or equal to about 79:1, greater than or equal to about 80:1, greater than or equal to about 81:1, greater than or equal to about 82:1, greater than or equal to about 83:1, greater than or equal to about 84:1, greater than or equal to about 86:1, greater than or equal to about 87:1, greater than or equal to about 88:1, greater than or equal to about 89:1, greater than or equal to about 90:1, greater than or equal to about 91:1, greater than or equal to about 92:1, greater than or equal to about 93:1, greater than or equal to about 94:1, greater than or equal to about 95:1, greater than or equal to about 96:1, greater than or equal to about 97:1, greater than or equal to about 98:1, greater than or equal to about 99:1, greater than or equal to about 73:1, greater than or equal to about 75:1, greater than or equal to about 77:1, greater than or equal to about 79:1, greater than or equal to about 81:1, greater than or equal to about 83:1, greater than or equal to about 85:1, greater than or equal to about 87:1, greater than or equal to about 89:1, greater than or equal to about 90:1, greater than or equal to about 91:1, greater than or equal to about 93:1, greater than or equal to about 95:1, greater than or equal to about 97:1, greater than or equal to about 99:1, or greater than or equal to about 100:1.

[0236] In an embodiment, in the semiconductor nanoparticles or the light-emitting layer including the semiconductor nanoparticles, the molar ratio of the sum of sulfur and selenium to indium [(S+Se):In] may be less than or equal to about 250:1, less than or equal to about 230:1, less than or equal to about 210:1, less than or equal to about 200:1, less than or equal to about 190:1, less than or equal to about 180:1, less than or equal to about 170:1, less than or equal to about 160:1, less than or equal to about 150:1, less than or equal to about 140:1, less than or equal to about 130:1, less than or equal to about 120:1, less than or equal to about 110:1, less than or equal to about 100:1, less than or equal to about 90:1, less than or equal to about 85:1, less than or equal to about 80:1, less than or equal to about 75:1, or less than or equal to about 70:1.

[0237] In an embodiment, in the semiconductor nanoparticles or the light emitting layer including the semiconductor nanoparticles, the molar ratio of indium to the sum of selenium and sulfur [In:(Se+S)] may be less than or equal to about 0.05:1, less than or equal to about 0.03:1, less than or equal to about 0.02:1, less than or equal to about 0.015:1, less than or equal to about 0.01:1, less than or equal to about 0.009:1, or less than or equal to about 0.008:1. The molar ratio of indium to the sum of selenium and sulfur [In:(Se+S)] may be greater than or equal to about 0.0005:1, greater than or equal to about 0.001:1, greater than or equal to about 0.003:1, greater than or equal to about 0.005:1, or greater than or equal to about 0.01:1.

[0238] In an embodiment, in the semiconductor nanoparticles or in the light-emitting layer, the molar ratio of zinc to the sum of selenium and sulfur [Zn:(Se+S)] may be less than or equal to about 2:1, less than or equal to about 1.9:1, less than or equal to about 1.8:1, less than or equal to about 1.7:1, less than or equal to about 1.6:1, less than or equal to about 1.5:1, less than or equal to about 1.4:1, less than or equal to about 1.3:1, less than or equal to about 1.2:1, less than or equal to about 1.19:1, less than or equal to about 1.18:1, less than or equal to about 1.17:1, less than or equal to about 1.16:1, less than or equal to about 1.15:1, less than or equal to about 1.14:1, less than or equal to about 1.13:1, less than or equal to about 1.12:1, or less than or equal to about 1.1:1. The molar ratio of zinc to the sum of selenium and sulfur [Zn:(Se+S)] may be greater than or equal to about 0.8:1, greater than or equal to about 0.9:1, greater than or equal to about 1:1, greater than or equal to about 1.05:1, greater than or equal to about 1.1:1, or greater than or equal to about 1.15:1.

[0239] In an embodiment, in the semiconductor nanoparticles or in the light emitting layer, the molar ratio of sulfur to selenium (S:Se) may be less than or equal to about 0.5:1, less than or equal to about 0.49:1, less than or equal to about 0.48:1, less than or equal to about 0.47:1, less than or equal to about 0.46:1, less than or equal to about 0.45:1, less than or equal to about 0.44:1, less than or equal to about 0.43:1, less than or equal to about 0.42:1, less than or equal to about 0.41:1, less than or equal to about 0.4:1, less than or equal to about 0.39:1, less than or equal to about 0.38:1, less than or equal to about 0.37:1, less than or equal to about 0.36:1, less than or equal to about 0.35:1, less than or equal to about 0.34:1, less than or equal to about 0.33:1, or less than or equal to about 0.32:1. The molar ratio of sulfur to selenium (S:Se) may be greater than or equal to about 0.15:1, greater than or equal to about 0.2:1, greater than or equal to about 0.21:1, greater than or equal to about 0.22:1, greater than or equal to about 0.23:1, greater than or equal to about 0.24:1, greater than or equal to about 0.25:1, greater than or equal to about 0.26:1, greater than or equal to about 0.27:1, or greater than or equal to about 0.28:1.

[0240] In an embodiment, in the semiconductor nanoparticles or the light-emitting layer including the semiconductor nanoparticles, the molar ratio of selenium to the sum of sulfur and selenium [Se:(Se+S)] may be greater than or equal to about 0.69:1, greater than or equal to about 0.7:1, greater than or equal to about 0.71:1, greater than or equal to about 0.72:1, greater than or equal to about 0.73:1, greater than or equal to about 0.74:1, or greater than or equal to about 0.75:1.

[0241] In the semiconductor nanoparticles or the light-emitting layer including the semiconductor nanoparticles, the molar ratio of selenium to the sum of sulfur and selenium [Se:(Se+S)] may be less than or equal to about 1:1, less than or equal to about 0.99:1, less than or equal to about 0.97:1, less than or equal to about 0.95:1, less than or equal to about 0.93:1, less than or equal to about 0.91:1, less than or equal to about 0.9:1, less than or equal to about 0.89:1, less than or equal to about 0.87:1, less than or equal to about 0.85:1, less than or equal to about 0.83:1, less than or equal to about 0.82:1, less than or equal to about 0.8:1, less than or equal to about 0.79:1, less than or equal to about 0.76:1, or less than or equal to about 0.74:1.

[0242] In the semiconductor nanoparticles or the light-emitting layer including the semiconductor nanoparticles, the molar ratio of sulfur to the sum of selenium and sulfur (S:(Se+S)) may be less than or equal to about 0.31:1, less than or equal to about 0.3:1, less than or equal to about 0.29:1, less than or equal to about 0.28:1, less than or equal to about 0.25:1, or less than or equal to about 0.2:1.

[0243] In an embodiment, in the semiconductor nanoparticles or the light-emitting layer including the semiconductor nanoparticles, the molar ratio of sulfur to the sum of selenium and sulfur (S:(Se+S)) may be greater than 0:1, greater than or equal to about 0.01:1, greater than or equal to about 0.03:1, greater than or equal to about 0.05:1, greater than or equal to about 0.07:1, greater than or equal to about 0.08:1, greater than or equal to about 0.1:1, greater than or equal to about 0.11:1, greater than or equal to about 0.13:1, greater than or equal to about 0.15:1, greater than or equal to about 0.17:1, greater than or equal to about 0.18:1, greater than or equal to about 0.2:1, greater than or equal to about 0.21:1, greater than or equal to about 0.23:1, or greater than or equal to about 0.26:1.

[0244] In the semiconductor nanoparticles or the light emitting layer including the semiconductor nanoparticles, a molar ratio of sulfur to selenium may be less than or equal to about 0.5:1.

[0245] An electroluminescent device based on semiconductor nanoparticles (hereinafter, may be referred to as a QD-LED) may emit light by application of voltage, and may include semiconductor nanocrystal particles as a light-emitting material. In a (photo)luminescent device including a light source, the semiconductor nanocrystal particles may be used as a wavelength conversion material that absorbs incident light emitted from the light source and emits light of a different wavelength spectrum (e.g., having a peak emission wavelength lower than the peak emission wavelength of the incident light).

[0246] QD-LEDs have attracted attention for use in next-generation display devices because they can express purer colors (red, green, and blue) and a wider color gamut than organic light-emitting diodes (OLEDs) that use light-emitting organic substances as emission centers. QD-LEDs can be manufactured at reduced manufacturing costs because their manufacture can include solution processes, and because the device uses inorganic-based materials, the QD-LEDs can exhibit improved stability. However, it is still desirable to develop technologies that can further improve device performance and lifespan.

[0247] It is also desirable to provide a light emitting device or display device including a light emitting layer that does not contain a substantial (significant) amount of harmful heavy metals. The electroluminescent device or light emitting device according to an embodiment is a self-emissive electroluminescent device that is configured to emit desired light, for example, by voltage application (for example, with or without a separate light source).

[0248] In schematically shown Figure 2 In an embodiment of the present invention, the electroluminescent device includes a first electrode 1, a second electrode 5 (e.g., spaced apart from or facing each other), and a light-emitting layer 3 disposed between the first electrode and the second electrode. In an embodiment, the light-emitting device of the embodiment may include a light source and a light-emitting layer, wherein the light source is configured to provide incident light to the light-emitting layer. The light-emitting layer includes semiconductor nanoparticles described herein. The light-emitting layer is configured to emit green light or blue light.

[0249] In an embodiment, the electron transport layer 4 may be disposed between the light emitting layer 3 and the second electrode 5. The electroluminescent device may further include a hole auxiliary layer 2 between the light emitting layer 3 and the first electrode 1. The electron auxiliary layer may be an electron transport layer. The hole auxiliary layer may include a hole transport layer (including, for example, an organic compound), a hole injection layer, or a combination thereof.

[0250] The details of the semiconductor nanoparticles are the same as described herein.

[0251] In the electroluminescent device of the embodiment, the first electrode 10 or the second electrode 50 may be provided on a (transparent) substrate 100. The transparent substrate may be a light extraction surface. Figure 3 and Figure 4 . refer to Figure 3 and 4 , the light emitting layer 30 may be disposed between the first electrode 10 and the second electrode 50. The second electrode 50 may include an electron injection conductor. The first electrode 10 may include a hole injection conductor. The work function of the electron / hole injection conductor included in the second electrode and the first electrode may be appropriately adjusted and is not particularly limited. For example, the second electrode may have a small work function and the first electrode may have a relatively large work function, or vice versa.

[0252] The electron / hole injection conductor (e.g., the second electrode or the first electrode) may include a metal-based material (e.g., a metal, a metal compound, an alloy, or a combination thereof) (aluminum, magnesium, tungsten, nickel, cobalt, platinum, palladium, calcium, or LiF), a metal oxide such as indium gallium oxide or indium tin oxide (ITO), or a conductive polymer (e.g., having a relatively high work function) such as polyethylenedioxythiophene, but is not limited thereto.

[0253] The first electrode, the second electrode, or a combination thereof may be a light-transmitting electrode or a transparent electrode. In an embodiment, both the first electrode and the second electrode may be light-transmitting electrodes. The electrode may be patterned. The first electrode, the second electrode, or a combination thereof may be disposed on a (e.g., insulating) substrate 100. The substrate 100 may be optically transparent (e.g., may have a light transmittance greater than or equal to about 50%, greater than or equal to about 60%, greater than or equal to about 70%, greater than or equal to about 80%, greater than or equal to about 85%, or greater than or equal to about 90% and, for example, less than or equal to about 99%, or less than or equal to about 95%). The substrate may further include an area for a blue pixel, an area for a red pixel, an area for a green pixel, or a combination thereof. A thin film transistor may be disposed in each of the stated areas of the substrate, and one of the source electrode and the drain electrode of the thin film transistor may be electrically connected to the first electrode or the second electrode.

[0254] The light-transmitting electrode may be disposed on a (eg, insulating) transparent substrate. The substrate may be a rigid or flexible substrate. Thus, the substrate may be plastic, glass, or metal.

[0255] The light transmittance of the light-transmitting electrode may be in a range of greater than or equal to about 50%, greater than or equal to about 60%, greater than or equal to about 70%, greater than or equal to about 80%, greater than or equal to about 80%, or greater than or equal to about 90%, for example, from about 80% to about 100%, from about 85% to about 95%, or a combination thereof.

[0256] The light-transmitting electrode may include, for example, a transparent conductor such as indium tin oxide (ITO) or indium zinc oxide (IZO), gallium indium tin oxide, zinc indium tin oxide, titanium nitride, polyaniline, or LiF / Mg:Ag, or a single layer or multiple layers of a metal film, but is not limited thereto. When one of the first electrode and the second electrode is an opaque electrode, the opaque electrode may be made of an opaque conductor such as aluminum (Al), lithium-aluminum (Li:Al) alloy, magnesium-silver alloy (Mg:Ag), or lithium fluoride-aluminum (LiF:Al). In an embodiment, the electrode may be an alloy electrode including materials, and the ratio between the materials may be appropriately adjusted, for example, it may range from 1:0.1 to 1:10, 1:0.2 to 1:5, 1:0.3 to 1:3, or a combination thereof.

[0257] In an embodiment, the first electrode or the second electrode may be a multilayer electrode. In an embodiment, the first electrode (or anode) may be a multilayer electrode comprising an electrode material, which is two or more layers, three or more layers, and 10 or less layers, or 5 or less layers. In an embodiment, the second electrode (or cathode) may be a multilayer electrode comprising an electrode material, which is two or more layers, three or more layers, and 10 or less layers, or 5 or less layers.

[0258] The multilayer electrode may include, for example, a light-transmitting conductive material such as indium tin oxide, an opaque conductive material such as aluminum (or a reflective electrode material), or a combination thereof. In an embodiment, the electrode (e.g., an anode or a cathode) may have a structure in which an opaque conductive material (or a reflective electrode material layer) is disposed between light-transmitting conductive materials (e.g., a transparent conductive material layer). In an embodiment, the electrode (e.g., an anode or a cathode) may have a structure in which a light-transmitting conductive material (e.g., a light-transmitting conductive material layer) is disposed between opaque conductive materials (or reflective electrode materials).

[0259] When a voltage is applied between the first and second electrodes, the light emitting layer may emit / extract light upward and downward by an electric field, and the light advancing to the reflective electrode may be reflected and emitted / extracted in the opposite direction.

[0260] In an embodiment, light may be emitted or extracted toward the cathode. In an embodiment, light may be emitted or extracted toward the anode.

[0261] The thickness of each electrode (e.g., the first electrode or the second electrode) is not particularly limited and can be appropriately selected in consideration of device efficiency. For example, the thickness of the electrode may be greater than or equal to about 5 nm, greater than or equal to about 10 nm, greater than or equal to about 20 nm, greater than or equal to about 30 nm, greater than or equal to about 40 nm, or greater than or equal to about 50 nm. For example, the thickness of the electrode may be less than or equal to about 100 micrometers (μm), less than or equal to about 90 μm, less than or equal to about 80 μm, less than or equal to about 70 μm, less than or equal to about 60 μm, less than or equal to about 50 μm, less than or equal to about 40 μm, less than or equal to about 30 μm, less than or equal to about 20 μm, less than or equal to about 10 μm, less than or equal to about 1 μm, less than or equal to about 900 nm, less than or equal to about 500 nm, or less than or equal to about 100 nm.

[0262] The method of forming the electrode is not particularly limited and may be appropriately selected according to the material. In an embodiment, the electrode may be formed by deposition, coating, or a combination thereof, but is not limited thereto.

[0263] The light emitting layer 3 or 30 is arranged on Figure 2 The first electrode 1 and the second electrode 5 (or for example, Figure 3 and 4 The light emitting layer includes semiconductor nanoparticles. The light emitting layer may include a single layer of a plurality of semiconductor nanoparticles. The light emitting layer may include a single layer of two or more (e.g., three or more) and 10 or less semiconductor nanoparticles.

[0264] The light-emitting layer may be patterned. In an embodiment, the patterned light-emitting layer may include a layer emitting blue light (e.g., disposed in a blue pixel in a display device to be described herein), a layer emitting red light (e.g., disposed in a red pixel in a display device to be described herein), and a layer emitting green light (e.g., disposed in a green pixel in a display device to be described herein), or a combination thereof. Each of the light-emitting layers may be separated from an adjacent light-emitting layer (e.g., optically) by a partition wall. In an embodiment, the partition wall, such as a black matrix, may be disposed between layers emitting different colors, such as a layer emitting red light, a layer emitting green light, and a layer emitting blue light. In an embodiment, the layer emitting red light, the layer emitting green light, and the layer emitting blue light may each be optically isolated.

[0265] The light emitting layer or the semiconductor nanoparticles may not include cadmium. The light emitting layer or the semiconductor nanoparticles may not include mercury, lead, or a combination thereof.

[0266] Details of the semiconductor nanoparticles included in the light emitting layer are described herein.

[0267] In the light emitting device, the thickness of the light emitting layer may be appropriately selected. In an embodiment, the light emitting layer 3 or 30 may include a single layer of quantum dots. In an embodiment, the light emitting layer 3 or 30 may include a single layer of quantum dots, for example, one, about two or more, about three or more, about four or more and 20 or less, 10 or less, 9 or less, 8 or less, 7 or less, or 6 or less quantum dots. The light emitting layer 3 or 30 may have a thickness of about 5 nm or more, for example, about 10 nm or more, about 20 nm or more, or about 30 nm or more and about 200 nm or less, for example, about 150 nm or less, about 100 nm or less, about 90 nm or less, about 80 nm or less, about 70 nm or less, about 60 nm or less, or about 50 nm or less. The light emitting layer 3 or 30 may have a thickness of, for example, about 10 nm to about 150 nm, for example, about 20 nm to about 100 nm, or for example, about 30 nm to about 50 nm.

[0268] The formation of the light emitting layer can be carried out by obtaining a composition including semiconductor nanoparticles configured to emit light of a desired wavelength, and applying or depositing the composition on a substrate or a charge assisting layer in a suitable manner (eg, by spin coating, inkjet printing, etc.).

[0269] In an embodiment, the electroluminescent device may include a charge assisting layer (eg, an electron assisting layer, a hole assisting layer, or a combination thereof) between the first electrode and the second electrode.

[0270] In an embodiment, the electroluminescent device may include a charge (hole or electron) auxiliary layer between the first electrode and the second electrode (e.g., the anode and the cathode). In an embodiment, the electroluminescent device may include a hole auxiliary layer 20 and / or an electron auxiliary layer 40 between the first electrode 10 and the light-emitting layer 30 and / or between the second electrode 50 and the light-emitting layer 30. (See Figure 3 and Figure 4 )

[0271] In an embodiment, the electroluminescent device may include a hole auxiliary layer. The hole auxiliary layer 20 may be located between the first electrode 10 and the light emitting layer 30. The hole auxiliary layer 20 may include a hole injection layer, a hole transport layer, and / or an electron blocking layer. The hole auxiliary layer 20 may be a single component layer or a multilayer structure in which adjacent layers include different components.

[0272] The HOMO energy level of the hole auxiliary layer 2 or 20 can match the HOMO energy level of the light emitting layer 3 or 30, so that the mobility of holes transferred from the hole auxiliary layer 2 or 20 to the light emitting layer 3 or 30 can be improved. In an embodiment, the hole auxiliary layer 2 or 20 may include a hole injection layer close to the first electrode 1 or 10 and a hole transport layer close to the light emitting layer 3 or 30.

[0273] The material of the hole auxiliary layer 2 or 20 (e.g., a hole transport layer or a hole injection layer) is not particularly limited. In an embodiment, the material of the hole auxiliary layer may include poly (9, 9-dioctyl-fluorene-co-N-(4-butylphenyl)-diphenylamine) (TFB), polyarylamine (polyarylamine), poly (N-vinyl carbazole) (PVK), poly (3,4-ethylenedioxythiophene) (PEDOT), poly (3,4-ethylenedioxythiophene): polystyrene sulfonate (PEDOT:PSS), polyaniline, polypyrrole, N,N,N',N'-tetrakis (4-methylbenzene) oxyphenyl)-benzidine (TPD), 4,4'-bis[N-(1-naphthyl)-N-phenyl-amino]biphenyl (α-NPD), 4,4',4"-tris[phenyl(m-tolyl)amino]triphenylamine (m-MTDATA), 4,4',4"-tris(N-carbazolyl)-triphenylamine (TCTA), 1,1-bis[(di-4-tolylamino)phenyl]cyclohexane (TAPC), p-type metal oxides (e.g., NiO, WO 3 、MoO 3 etc.), carbon-based materials such as graphene oxide, or combinations thereof, but are not limited thereto.

[0274] The electron blocking layer (EBL) may include, for example, poly(3,4-ethylenedioxythiophene):poly(styrene sulfonate) (PEDOT:PSS), poly(9,9-dioctyl-fluorene-co-N-(4-butylphenyl)-diphenylamine) (TFB), polyarylamine (polyarylamine), poly(N-vinylcarbazole), polyaniline, polypyrrole, N,N,N',N'-tetrakis(4-methoxyphenyl)-benzidine (TPD), 4,4'-bis[N-(1-naphthyl)-N-phenyl-amino]biphenyl (α-NPD), m-MTDATA, 4,4',4"-tris(N-carbazolyl)-triphenylamine (TCTA), or a combination thereof, but is not limited thereto.

[0275] In the hole auxiliary layer, the thickness of each layer can be appropriately selected. In an embodiment, the thickness of each layer can be greater than or equal to about 5 nm, greater than or equal to about 10 nm, greater than or equal to about 15 nm, or greater than or equal to about 20 nm and less than or equal to about 50 nm, less than or equal to about 40 nm, less than or equal to about 50 nm, less than or equal to about 35 nm, or less than or equal to about 30 nm, but is not limited thereto.

[0276] In an embodiment, the second electrode may be a cathode, and the electron auxiliary layer 4 or 40 may be disposed between the light emitting layer 3 or 30 and the second electrode 5 or 50. The electron auxiliary layer 4 or 40 may include, for example, an electron injection layer, an electron transport layer, a hole blocking layer, or a combination thereof. The electron auxiliary layer may be, for example, an electron injection layer (EIL) that facilitates electron injection, an electron transport layer (ETL) that facilitates electron transport, a hole blocking layer (HBL) that blocks hole movement, or a combination thereof.

[0277] In an embodiment, an electron injection layer may be disposed between the electron transport layer and the cathode. In an embodiment, a hole blocking layer may be disposed between the light emitting layer and the electron transport (injection) layer, but is not limited thereto. The thickness of each layer may be appropriately selected. For example, the thickness of each layer may be greater than or equal to about 1 nm and less than or equal to about 500 nm, but is not limited thereto. The electron injection layer may be an organic layer formed by deposition. The electron transport layer may include inorganic oxide nanoparticles or may be an organic layer formed by deposition.

[0278] The electron transport layer (ETL), the hole blocking layer (HBL), and / or the electron injection layer may include, for example, 1,4,5,8-naphthalene-tetracarboxylic dianhydride (NTCDA), bathocuproine (BCP), tris[3-(3-pyridyl)- yl]borane (3TPYMB), LiF, Alq 3 , Gaq 3 、Inq 3 、Znq 2 、Zn(BTZ) 2 、BeBq 2 , ET204 (8-(4-(4,6-di(naphthalene-2-yl)-1,3,5-triazine-2-yl)phenyl)quinolone), 8-hydroxyquinoline lithium (Liq), n-type metal oxides (e.g., ZnO or HfO 2 ), or a combination thereof, but not limited thereto.

[0279] The electron assist layer 4 or 40 may include an electron transport layer including a plurality of metal oxide nanoparticles. The nanoparticles may include a metal oxide including zinc.

[0280] The metal oxide may include zinc oxide, zinc magnesium oxide, or a combination thereof. The metal oxide may include Zn 1- x M xO (wherein M is Mg, Ca, Zr, W, Li, Ti, Y, Al, Co, or a combination thereof, and 0≤x≤0.5). In an embodiment, M may be magnesium (Mg). In an embodiment, x may be greater than or equal to about 0.01 and less than or equal to about 0.3, for example, less than or equal to about 0.25, less than or equal to about 0.2, or less than or equal to about 0.15.

[0281] In an embodiment, the absolute value of LUMO of the aforementioned semiconductor nanoparticles included in the light emitting layer may be smaller than the absolute value of LUMO of the metal oxide. The metal oxide nanoparticles may have an average size of greater than or equal to about 1 nm, for example, greater than or equal to about 1.5 nm, greater than or equal to about 2 nm, greater than or equal to about 2.5 nm, or greater than or equal to about 3 nm and less than or equal to about 10 nm, less than or equal to about 9 nm, less than or equal to about 8 nm, less than or equal to about 7 nm, less than or equal to about 6 nm, or less than or equal to about 5 nm.

[0282] In an embodiment, the thickness of each of the electron auxiliary layer 4 or 40 (e.g., an electron injection layer, an electron transport layer, or a hole blocking layer) may be greater than or equal to about 5 nm, greater than or equal to about 6 nm, greater than or equal to about 7 nm, greater than or equal to about 8 nm, greater than or equal to about 9 nm, greater than or equal to about 10 nm, greater than or equal to about 11 nm, greater than or equal to about 12 nm, greater than or equal to about 13 nm, greater than or equal to about 14 nm, greater than or equal to about 15 nm, greater than or equal to about 16 nm, greater than or equal to about 17 nm, greater than or equal to about 18 nm, greater than or equal to about 19 nm, greater than or equal to about 20 nm, greater than or equal to about 21 nm, greater than or equal to about 22 nm, greater than or equal to about 23 nm, greater than or equal to about 24 nm, greater than or equal to about 25 nm, greater than or equal to about 26 nm, greater than or equal to about 27 nm, greater than or equal to about 28 nm, greater than or equal to about 29 nm, greater than or equal to about 30 nm, greater than or equal to about 31 nm, greater than or equal to about 32 nm, greater than or equal to about 33 nm, greater than or equal to about 34 nm, greater than or equal to about 35 nm, greater than or equal to about 36 nm, greater than or equal to about 37 nm, greater than or equal to about 38 nm, greater than or equal to about 39 nm, greater than or equal to about 40 nm, greater than or equal to about 41 nm, greater than or equal to about 42 nm, greater than or equal to about 43 nm, greater than or equal to about 44 nm, greater than or equal to about 45 nm, greater than or equal to about 46 nm, greater than or equal to about 47 nm, Equal to about 17nm, greater than or equal to about 18nm, greater than or equal to about 19nm, or greater than or equal to about 20nm and less than or equal to about 120nm, less than or equal to about 110nm, less than or equal to about 100nm, less than or equal to about 90nm, less than or equal to about 80nm, less than or equal to about 70nm, less than or equal to about 60nm, less than or equal to about 50nm, less than or equal to about 40nm, less than or equal to about 30nm, or less than or equal to about 25nm, but is not limited thereto.

[0283] The device according to the embodiment may have a normal structure. In the embodiment, reference Figure 3, the device includes a first electrode 10 disposed on a transparent substrate 100, such as a metal oxide-based (i.e., metal oxide) transparent electrode (e.g., an ITO electrode), and a second electrode 50 (e.g., facing the first electrode) may include a conductive metal (e.g., Mg or Al) (e.g., having a relatively low work function). A hole auxiliary layer 20 (e.g., a hole injection layer such as PEDOT:PSS, a p-type metal oxide, or a combination thereof; a hole transport layer such as TFB, PVK, or a combination thereof; or a combination thereof) may be disposed between the first electrode 10 and the light emitting layer 30. The hole injection layer may be close to the first electrode, and the hole transport layer may be close to the light emitting layer. An electron auxiliary layer 40, such as an electron injection layer / transport layer, may be disposed between the light emitting layer 30 and the second electrode 50.

[0284] In an embodiment, the device may have an inverted structure. For example, referring to Figure 4 , the second electrode 50 is disposed on a transparent substrate 100, for example, a metal oxide-based transparent electrode (e.g., ITO), and the first electrode 10 may include a metal (e.g., Au or Ag) (e.g., having a relatively high work function). For example, an (optionally doped) n-type metal oxide (crystalline Zn metal oxide) may be disposed between the second electrode 50 and the light-emitting layer 30 as an electron auxiliary layer 40 (e.g., an electron transport layer). The hole auxiliary layer 20 (e.g., a hole transport layer including TFB, PVK, or a combination thereof; a hole transport layer including MoO 3 or a hole injection layer of other p-type metal oxides; or a combination thereof) may be disposed between the first electrode 10 and the light emitting layer 30 .

[0285] The electroluminescent device of the embodiment can be prepared by a suitable method. In an embodiment, the electroluminescent device can be prepared by providing a first (or second) electrical conductor, optionally forming a charge auxiliary layer thereon (e.g., by deposition or coating), and forming a light-emitting layer (e.g., a pattern thereof) including the aforementioned plurality of semiconductor nanoparticles, optionally providing a charge auxiliary layer, and providing a second (or first) electrical conductor (e.g., via deposition or coating).

[0286] The formation of the electric conductor and the charge assisting layer (eg, the hole assisting layer or the electron assisting layer) may be appropriately performed and is not particularly limited.

[0287] In an embodiment, the electroluminescent device may exhibit improved luminescent properties (e.g., improved electroluminescent properties) or a combination thereof. In an embodiment, the electroluminescent device may exhibit a maximum external quantum efficiency (max EQE) of greater than or equal to about 6%, greater than or equal to about 7%, greater than or equal to about 8%, greater than or equal to about 9%, greater than or equal to about 9.5%, greater than or equal to about 10%, greater than or equal to about 10.2%, greater than or equal to about 10.5%, greater than or equal to about 11%, greater than or equal to about 11.5%, greater than or equal to about 12%, greater than or equal to about 12.5%, greater than or equal to about 13%, greater than or equal to about 13.5%, or greater than or equal to about 14%. In one aspect, the electroluminescent device may exhibit a maximum EQE in the range of about 6% to about 50%, about 7% to about 40%, about 8% to about 30%, about 9% to about 20%, or a combination thereof.

[0288] In embodiments, the electroluminescent device may exhibit a light intensity of greater than or equal to about 50,000 candelas per square meter (cd / m 2 ), a maximum brightness (max brightness) of greater than or equal to about 60,000 nits, greater than or equal to about 70,000 nits, greater than or equal to about 80,000 nits, greater than or equal to about 88,000 nits, greater than or equal to about 90,000 nits, greater than or equal to about 95,000 nits, greater than or equal to about 100,000 nits, greater than or equal to about 105,000 nits, greater than or equal to about 110,000 nits, greater than or equal to about 115,000 nits, greater than or equal to about 120,000 nits, greater than or equal to about or 125,000 nits.

[0289] The electroluminescent device may exhibit the aforementioned max EQE and the aforementioned max brightness.

[0290] The electroluminescent device may exhibit relatively improved lifetime properties. In an embodiment, the electroluminescent device may be provided with a predetermined initial brightness (e.g., about 146 nits (candela / square meter, cd / m 2 The electroluminescent device may exhibit a T50 of about 150 hours or more, about 300 hours or more, about 310 hours or more, about 350 hours or more, about 380 hours or more, about 400 hours or more, about 450 hours or more, or about 500 hours or more, as measured when the device is operated at a predetermined initial brightness (e.g., about 146 nits (candela / square meter, cd / m 2The electroluminescent device may exhibit a T90 of greater than or equal to about 20 hours, greater than or equal to about 30 hours, greater than or equal to about 45 hours, greater than or equal to about 50 hours, greater than or equal to about 75 hours, greater than or equal to about 100 hours, greater than or equal to about 125 hours, greater than or equal to about 150 hours, greater than or equal to about 175 hours, or greater than or equal to about 200 hours, as measured when the light is running at a constant light intensity of about 100 nits, about 250 nits, about 650 nits, or about 2700 nits.

[0291] In embodiments, the T50 may be about 150 to 5000 hours, about 200 to 300 hours, about 400 to 4000 hours, about 450 to 600 hours, about 500 to 3500 hours, about 750 to 2000 hours, about 1000 to 1500 hours, or a combination thereof.

[0292] In an embodiment, the T90 may range from about 30 to 2500 hours, about 45 to 2000 hours, about 50 to 1500 hours, about 75 to 1000 hours, about 100 to 800 hours, about 150 to 700 hours, about 200 to 500 hours, about 300 to 400 hours, or a combination thereof.

[0293] In an embodiment, a display device includes an electroluminescent device described herein.

[0294] The display device may include a first pixel and a second pixel configured to emit light different from the first pixel. The first pixel, the second pixel, or a combination thereof may include an electroluminescent device of an embodiment. The display device may include an AR / VR device, a mobile device, a monitor, a laptop, a television, an electronic sign, a camera, or an electronic component (e.g., for an automobile).

[0295] Hereinafter, specific embodiments of the present invention are provided. However, the embodiments described below are only for specific illustration or description of the present invention, and thus the scope of the present invention should not be limited.

[0296] Example

[0297] Analytical methods

[0298] 1. Photoluminescence analysis and absolute quantum yield (QY) measurement

[0299] Photoluminescence spectroscopy analysis of semiconductor nanoparticles was performed using a Hitachi F-7000 spectrometer or a Hamamatsu instrument at room temperature under irradiation with light having a wavelength of 400 nm (for semiconductor nanoparticles emitting blue light).

[0300] 2. Transmission Electron Microscopy (TEM) Analysis

[0301] Transmission electron microscopy images of the as-prepared semiconductor nanoparticles were obtained by using a UT F30 Tecnai electron microscope.

[0302] The acquired TEM images were analyzed with the Image J program or with an in-house software based on the Python language to measure the particle size and shape factor.

[0303] 3. Inductively coupled plasma (ICP) analysis

[0304] Inductively coupled plasma-atomic emission spectrometry (ICP-AES) analysis was performed using Shimadzu ICPS-8100.

[0305] 4. Electroluminescence Measurement

[0306] With voltage applied, the voltage-dependent current was measured with a Keithley 2635B source meter, and the electroluminescence was measured using a CS2000 spectrometer.

[0307] 5. Lifespan evaluation

[0308] For T50 (hours), the time taken for the device to reach 50% of the initial luminance (or photocurrent density) (100%) when the device is initially driven at a predetermined luminance (eg, 650 nits) is measured.

[0309] For T90(h), the time taken for the device to reach 90% of the initial brightness (or photocurrent density) (100%) when the device is initially driven at a predetermined brightness (eg, 650 nits) is measured.

[0310] 6.TGA analysis

[0311] The samples were heated from 30°C to 600°C in nitrogen (N2) using a Discovery TGA (from TA instruments) at a heating rate of 10°C / min. 2 ) atmosphere for TGA analysis.

[0312] 7.GC analysis

[0313] GC-MS analysis was performed using a gas chromatograph (GC, Agilent 7890B) coupled with a mass spectrometer (MS, Agilent 5977A).

[0314] After separation using ethanol, 1 mL of the crude dispersion containing the prepared semiconductor nanoparticles was vacuum dried, and 0.1 mg of the semiconductor nanoparticles and 1 μL (microliter) of TMAH (trimethylammonium hydroxide) were mixed and kept in a hood for 2 minutes and subjected to py-GC / MS measurement.

[0315] -Pyrolyzer: 450℃

[0316] - Column: 30m X 0.25mm X 0.25mm (UA5)

[0317] -Flow: He (1mL / min)

[0318] - Inlet temperature: 300℃

[0319] -Analyzer: quadrupole (range: 10 to 550 m / z)

[0320] The following syntheses were performed under an inert gas atmosphere (eg, under nitrogen) unless otherwise stated. Precursor amounts are provided as molar amounts unless otherwise stated.

[0321] Reference example: Synthesis of ZnMgO nanoparticles

[0322] Zinc acetate dihydrate and magnesium acetate tetrahydrate were added to a reactor containing dimethyl sulfoxide and heated at 60°C in air. Subsequently, an ethanol solution of tetramethylammonium hydroxide pentahydrate was added to the reactor. After the mixture was stirred for 1 hour, a precipitate was formed and separated from the reaction mixture using a centrifuge. The precipitate was dispersed in ethanol to obtain Zn 1- x Mg x O nanoparticles (x=0.15). The obtained nanoparticles were subjected to transmission electron microscopy analysis. The particles had an average size of about 3 nm.

[0323] Synthesis Example 1-1:

[0324] [1] Synthesis of the first semiconductor nanocrystals:

[0325] Selenium and tellurium were dispersed in trioctylphosphine (TOP) to obtain 2 molar (M) Se / TOP stock solution (stock solution) and 0.1 M Te / TOP stock solution, respectively.

[0326] In a 300mL reaction flask containing trioctylamine (TOA), 4.5mmol zinc acetate and oleic acid are added together and heated to 120 degrees Celsius under vacuum. After 1 hour, the atmosphere in the reactor is changed to an inert gas, for example, nitrogen is added to the previously vacuumed reaction flask. The flask is heated to the reaction temperature (300°C), the prepared Se / TOP stock solution and Te / TOP stock solution are injected with a Te:Se molar ratio of 1:15, and the reaction is allowed to proceed for a predetermined time (e.g., about one hour) after reaching the reaction temperature. When the reaction is complete, the reaction solution is cooled to room temperature, and ethanol is added to promote precipitation. The resulting mixture is centrifuged to separate and obtain ZnSeTe cores, which are dispersed in hexane. The average size of the core is about 3nm.

[0327] [2] Synthesis of the second semiconductor nanocrystal:

[0328] Zinc acetate was added together with oleic acid to the 300 mL reaction flask containing TOA, and the resulting mixture was heated at 120° C. under vacuum. Nitrogen (N 2 ), and during the time period of heating the flask to the reaction temperature (280°C), the hexane dispersion of the (above) ZnSeTe core is added to the reaction flask, and then the Se / TOP stock solution is added. When the temperature of the flask reaches the reaction temperature, the reaction continues for a predetermined time (e.g., about one hour). When the reaction is completed, the reaction solution is cooled to room temperature, and ethanol is added to promote precipitation. The resulting mixture is centrifuged to separate and obtain first particles (including the first semiconductor nanocrystal and the second semiconductor nanocrystal). The first particles thus obtained are dispersed in toluene and then washed with ethanol. The washed first particles are separated by centrifugation and dispersed in hexane.

[0329] [3] Formation of semiconductor nanocrystal layer:

[0330] Zinc acetate was added together with oleic acid to a 300 mL reaction flask containing TOA, and the reaction mixture was vacuum treated at 120°C to obtain a zinc precursor.

[0331] In a separate 300 mL reaction flask containing TOA, the flask was vacuum treated at 120° C. Nitrogen (N 2 ), and the flask was heated to 220° C. (first temperature). The zinc precursor, the hexane dispersion of the first particles, and dodecanethiol as a sulfur precursor were added to the flask, and the flask was heated to 340° C. and the reaction was allowed to continue for 60 minutes.

[0332] The amount of dodecanethiol used was 0.5 mol based on 1 mol of the zinc precursor.

[0333] When the reaction was completed, the reaction solution was cooled to room temperature, and ethanol was added thereto to promote precipitation. The resulting mixture was centrifuged to separate and obtain semiconductor nanoparticles.

[0334] ICP-AES analysis of the obtained semiconductor nanoparticles was performed, and the results are shown in Table 1. TEM analysis, photoluminescence analysis, and TGA analysis of the obtained semiconductor nanoparticles were performed, and the results are shown in Tables 2 and 4.

[0335] The GC-MS analysis of the obtained semiconductor nanoparticles was performed and the results are summarized in Tables 3 and Figure 5A middle.

[0336] Synthesis Example 1-2:

[0337] Semiconductor nanoparticles were prepared in the same manner as in Synthesis Example 1-1, except that in the formation of the semiconductor nanocrystal layer, the reaction temperature was set to 320° C. GC-MS analysis of the obtained semiconductor nanoparticles was performed, and the results are listed in Tables 3 and Figure 5A middle.

[0338] Synthesis Example 2:

[0339] Semiconductor nanoparticles were prepared in the same manner as in Synthesis Example 1-1, except that the preparation and use of the zinc precursor for the semiconductor nanocrystal layer were performed as follows: zinc acetate was added together with oleic acid to a 300 mL reaction flask containing TOA, which was vacuum-treated at 120° C. to obtain zinc oleate (ZnOa), and in a similar manner, ethylhexanoic acid was used to obtain zinc ethylhexanoate (Zn-EHa), and the two types of zinc precursors obtained were used together at a molar ratio of ZnOa:Zn-EHa of 21:4.

[0340] ICP-AES analysis of the obtained semiconductor nanoparticles was performed, and the results are shown in Table 1. TEM analysis, photoluminescence analysis, and TGA analysis of the obtained semiconductor nanoparticles were performed, and the results are shown in Tables 2 and 4.

[0341] Comparative Synthesis Example 1:

[0342] Semiconductor nanoparticles were prepared in the same manner as in Synthesis Example 1-1, except that S / TOP (1M) was used as a sulfur precursor instead of dodecanethiol.

[0343] ICP-AES analysis of the obtained semiconductor nanoparticles was performed, and the results are shown in Table 1. TEM analysis, photoluminescence analysis, and TGA analysis of the obtained semiconductor nanoparticles were performed, and the results are shown in Tables 2 and 4.

[0344] Comparative Synthesis Examples 2-1 and 2-2:

[0345] Semiconductor nanoparticles were prepared in the same manner as in Synthesis Example 1-1, except that in the formation of the semiconductor nanocrystal layer, the reaction temperature was set to 280°C and 0.8 mol S / TOP was additionally injected per 1 mol of Zn (Synthesis Comparative Example 2-1), and the reaction temperature was set to 300°C (for Synthesis Comparative Example 2-2).

[0346] The GC-MS analysis of the obtained semiconductor nanoparticles was performed and the results are summarized in Tables 3 and Figure 5A middle.

[0347] Comparative Synthesis Example 3:

[0348] Semiconductor nanoparticles were prepared in the same manner as in Synthesis Example 1-1, except that in the formation of the semiconductor nanocrystal layer, the reaction temperature was set to 280°C.

[0349] The GC-MS analysis of the obtained semiconductor nanoparticles was performed and the results are summarized in Tables 3 and Figure 5B middle.

[0350] Comparative Synthesis Example 4:

[0351] Semiconductor nanoparticles were prepared in the same manner as in Synthesis Example 1-1, except that in the formation of the semiconductor nanocrystal layer, the reaction temperature was changed to 320°C, and the sulfur precursor (i.e., dodecanethiol) was added only after the temperature in the reaction flask reached the reaction temperature, rather than at the first temperature. It was confirmed that the ZnS shell layer was not suitably formed, resulting in semiconductor nanoparticles with relatively insufficient properties.

[0352] Table 1

[0353] S:(S+Se) S:Te Zn:Se (S+Se):Zn Comparative Synthesis Example 1 0.33:1 73:1 1.84:1 0.81:1 Synthesis Example 1-1 0.44:1 107:1 1.83:1 0.97:1 Synthesis Example 2 0.38:1 90:1 1.77:1 0.91:1

[0354] Table 2

[0355] PWL(nm) QY FWHM TGA organic content (weight %) Comparative Synthesis Example 1 462 96 45 14.8 Synthesis Example 1-1 462 96 42 12.57 Synthesis Example 2 460 91 41 10.184

[0356] PWL: Peak emission wavelength

[0357] QY: Quantum yield (%)

[0358] FWHM: Half Width (nm)

[0359] TGA Organic Amount: The amount of organic matter of the semiconductor nanoparticles as measured in thermogravimetric analysis.

[0360] The results of Table 2 show that, compared with the semiconductor nanoparticles of Comparative Synthesis Example 1, the semiconductor nanoparticles of Synthesis Example 1-1 and Synthesis Example 2 have reduced organic material contents.

[0361] Table 3

[0362] OA DDT Comparative Synthesis Example 2-1 25.2% 74.8% Comparative Synthesis Example 2-2 82.1% 17.9% Comparative Synthesis Example 3 41.3% 58.7% Synthesis Example 1-1 98.7% 1.3% Synthesis Example 1-2 96.2% 3.8%

[0363] OA: Area percentage of the peak for oleate ligand (first ligand) relative to the total area of ​​the peaks for ligands derived from oleate ligand (first ligand) and dodecanethiol ligand (second ligand) (OA peak position: 13.15)

[0364] DDT: Area percentage of the peak for the thiolate ligand (second ligand) relative to the total area of ​​the peaks for the ligands derived from the oleate ligand (first ligand) and the dodecanethiol ligand (second ligand) (DDT peak position: 10.74)

[0365] Figure 5A , 5B The results of Table 3 show that the semiconductor nanoparticles of Synthesis Example 1-1 and Synthesis Example 1-2 include organic ligands derived from thiol and organic ligands derived from oleic acid, but the amount of organic ligands derived from thiol is limited. In contrast, the semiconductor nanoparticles of Comparative Synthesis Examples 2-1, 2-2 and 3 contain significantly more organic ligands derived from thiol.

[0366] Table 4

[0367] Average size (diameter) (nm) Roundness Circularity Solidity Comparative Synthesis Example 1 10.25 0.804 0.714 0.975 Synthesis Example 1-1 9.74 0.836 0.754 0.981 Synthesis Example 2-1 9.97 0.834 0.757 0.98

[0368] Synthesis Example 3:

[0369] Semiconductor nanoparticles were prepared in the same manner as in Synthesis Example 1-1, except that octanethiol (OT) was used as a sulfur precursor instead of dodecanethiol in the formation of the semiconductor nanocrystal layer.

[0370] Synthesis Example 4:

[0371] Semiconductor nanoparticles were prepared in the same manner as in Synthesis Example 1-1, except that 2-ethylhexanethiol (EHT) was used as a sulfur precursor instead of dodecanethiol in the formation of the semiconductor nanocrystal layer.

[0372] Synthesis Example 5:

[0373] Semiconductor nanoparticles were prepared in the same manner as in Synthesis Example 1-1, except that tetradecanethiol (TDT) was used as a sulfur precursor instead of dodecanethiol in the formation of the semiconductor nanocrystal layer.

[0374] Preparation of electroluminescent devices

[0375] Device Example 1-1

[0376] A light emitting device was manufactured according to the following method using the plurality of semiconductor nanoparticles of Synthesis Example 1-1.

[0377] On a glass substrate deposited with indium tin oxide (ITO) (anode), a poly(3,4-ethylenedioxythiophene):polystyrene sulfonate (PEDOT:PSS) solution (HCStarks) was spin-coated, followed by a poly[(9,9-dioctylfluorene-co-(4,4′-(N-4-butylphenyl)diphenylamine] solution (TFB) (Sumitomo), and then heat-treated to provide a hole injection layer (HIL) having a thickness of 30 nm and a hole transport layer (HTL) having a thickness of 25 nm, respectively.

[0378] The semiconductor nanoparticles obtained by Synthesis Example 1-1 were dispersed in octane, and spin-coated on the HTL and heat-treated to provide a light-emitting film having a thickness of 25 nm. A ZnO2 film prepared by Reference Example was formed on the light-emitting film. 1- x Mg x An electron transport layer (ETL) of O nanoparticles was formed, the ETL having a thickness of about 28 nm. Aluminum (Al) was then vacuum deposited on the ETL to provide a second electrode.

[0379] The obtained device was confirmed to emit blue light when voltage was applied. The electroluminescent properties of the obtained device were evaluated, and the results are listed in Table 5.

[0380] Device Examples 1-2

[0381] A light-emitting device was manufactured according to the same procedure as in Device Example 1-1, except that a plurality of semiconductor nanoparticles of Synthesis Example 1-2 were used instead of the semiconductor nanoparticles of Synthesis Example 1-1 for forming a light-emitting film.

[0382] The obtained device was confirmed to emit blue light when voltage was applied. The electroluminescent properties were measured for the obtained device, and the results are listed in Table 5.

[0383] Device Example 2

[0384] A light-emitting device was manufactured according to the same procedure as in Device Example 1-1, except that a plurality of semiconductor nanoparticles of Synthesis Example 2 were used instead of the semiconductor nanoparticles of Synthesis Example 1-1 for forming a light-emitting film.

[0385] The obtained device was confirmed to emit blue light when voltage was applied. The electroluminescent properties were measured for the obtained device, and the results are listed in Table 5.

[0386] Device Comparison Example 1

[0387] A light-emitting device was manufactured according to the same procedure as in Device Example 1-1, except that a plurality of semiconductor nanoparticles of Comparative Synthesis Example 1 were used instead of the semiconductor nanoparticles of Synthesis Example 1-1 for forming a light-emitting film.

[0388] The obtained device was confirmed to emit blue light when voltage was applied. The electroluminescent properties were measured for the obtained device, and the results are listed in Table 5.

[0389] Device Comparison Example 2-1

[0390] A light-emitting device was manufactured according to the same procedure as in Device Example 1-1, except that a plurality of semiconductor nanoparticles of Comparative Synthesis Example 2-1 were used instead of the semiconductor nanoparticles of Synthesis Example 1-1 for forming a light-emitting film.

[0391] The obtained device was confirmed to emit blue light when voltage was applied. The electroluminescent properties were measured for the obtained device, and the results are listed in Table 5.

[0392] Table 5

[0393]

[0394]

[0395] Max EQE: Maximum external quantum efficiency (%)

[0396] Max brightness: Maximum brightness (cd / m 2 )

[0397] The results of Table 5 demonstrate that the devices of the Examples exhibit significantly improved electroluminescent properties and extended lifetime (stability) compared to the devices of the Comparative Examples.

[0398] Experimental Example 1 (Hole Only Device (HOD), HOD Fabrication)

[0399] HOD was manufactured in the same manner as in Device Example 2 and Comparative Device Example 1, except that a hole auxiliary layer using a small molecule organic hole transport material (eg, HAT-CN, etc.) was formed instead of an electron transport layer, and the thickness of the quantum dot emission layer was 40 nm.

[0400] Experiments were conducted to measure current while applying voltage to the fabricated HOD. The results for the HOD are listed in Table 6.

[0401] Table 6

[0402] Semiconductor nanoparticles in the light-emitting layer of HOD HOD 8V, 40nm luminous layer Synthesis Example 2 <![CDATA[4.73mA / cm 2 ]]> Comparative Synthesis Example 1 <![CDATA[0.36mA / cm 2 ]]>

[0403] The results of Table 6 demonstrate that the semiconductor nanoparticles of Synthesis Example 2 exhibit improved hole transport results compared to the semiconductor nanoparticles of Synthesis Comparative Example 1.

[0404] Device Example 3

[0405] A light-emitting device was manufactured according to the same procedure as in Device Example 1-1, except that a plurality of semiconductor nanoparticles of Synthesis Example 3 (prepared using OT as a sulfur precursor) were used instead of the semiconductor nanoparticles of Synthesis Example 1-1 for forming a light-emitting film.

[0406] The obtained device was confirmed to emit blue light when voltage was applied. The electroluminescent properties and lifetime of the device were measured. The results confirmed that the maximum brightness of the device was 1.5 times and 2 times higher than that of Comparative Examples 1 and 2-1, respectively; the T90 of the device was 2.75 times and 7.31 times longer than that of Comparative Examples 1 and 2-1, respectively; and the T50 of the device was 1.62 times and 2.33 times longer than that of Comparative Examples 1 and 2-1, respectively.

[0407] Device Example 4

[0408] A light-emitting device was manufactured according to the same procedure as in Device Example 1-1, except that a plurality of semiconductor nanoparticles of Synthesis Example 4 (prepared using EHT as a sulfur precursor) were used instead of the semiconductor nanoparticles of Synthesis Example 1-1 for forming a light-emitting film.

[0409] The obtained device was confirmed to emit blue light when voltage was applied. The electroluminescent properties and lifetime of the device were measured. The results confirmed that the maximum brightness of the device was substantially equal to and 1.31 times higher than those of Comparative Examples 1 and 2-1, respectively; the T90 of the device was 3.90 times and 10.35 times longer than those of Comparative Examples 1 and 2-1, respectively; and the T50 of the device was 3.83 times and 5.49 times longer than those of Comparative Examples 1 and 2-1, respectively.

[0410] Device Example 5

[0411] A light-emitting device was manufactured according to the same procedure as in Device Example 1-1, except that a plurality of semiconductor nanoparticles of Synthesis Example 5 (prepared using TDT as a sulfur precursor) were used instead of the semiconductor nanoparticles of Synthesis Example 1-1 for forming a light-emitting film.

[0412] The obtained device was confirmed to emit blue light when voltage was applied. The maximum brightness and lifetime of the device were measured. The results confirmed that the maximum brightness of the device was 1.5 times and 2.1 times higher than that of Comparative Examples 1 and 2-1, respectively; the T90 of the device was 3.36 times and 8.91 times longer than that of Comparative Examples 1 and 2-1, respectively; and the T50 of the device was 1.69 times and 2.42 times longer than that of Comparative Examples 1 and 2-1, respectively.

[0413] While the present disclosure has been described with respect to what are presently considered to be practical example embodiments, it will be understood that the invention is not limited to the disclosed embodiments, but is intended to cover various modifications and equivalent arrangements included within the spirit and scope of the appended claims.

Claims

1. A method for preparing semiconductor nanoparticles, comprising: contacting a zinc precursor and a sulfur precursor in the presence of first particles at a predetermined temperature to form a semiconductor nanocrystal layer containing zinc sulfide on the first particles, Wherein the first particle comprises: II-VI compounds containing zinc and selenium, wherein the predetermined temperature includes a temperature greater than 300°C and less than or equal to 380°C, and The sulfur precursor includes a C3-C50 thiol compound or a combination thereof.

2. The method of claim 1, wherein the sulfur precursor does not include sulfur-trioctylamine (S-TOA), sulfur-trioctylphosphine (S-TOP), sulfur-octadecene (S-ODE), or a combination thereof.

3. The method of claim 1, wherein the first particles further comprise a Group III-V compound.

4. The method of claim 1, wherein the first particles include first semiconductor nanocrystals and second semiconductor nanocrystals, The first semiconductor nanocrystal includes a II-VI group compound containing zinc, selenium, and tellurium; or a III-V group compound containing indium and phosphorus, and The second semiconductor nanocrystals include a Group II-VI compound including zinc and selenium.

5. The method of claim 1, wherein the method further comprises adding the first particles, the zinc precursor, and the sulfur precursor to a reaction medium comprising an organic solvent at a first temperature, the first temperature being greater than or equal to 180° C. and less than 320° C.; Optionally, before being added to the reaction medium, the first particles are washed with an organic solvent and then dispersed in a dispersing solvent.

6. The method of claim 1, wherein the predetermined temperature is greater than 335°C and less than or equal to 360°C.

7. The method of claim 1, wherein the sulfur precursor comprises ethylhexyl mercaptan, decanethiol, undecanethiol, dodecanethiol, tetradecanethiol, hexadecanethiol, octadecanethiol, or a mixture thereof.

8. The method of claim 1, wherein the zinc precursor comprises a compound represented by Chemical Formula 1: Chemical formula 1 ACOO-Zn-OOCB In Chemical Formula 1, A and B are the same or different, and are each independently a substituted or unsubstituted linear or branched C1-C60 aliphatic hydrocarbon group, or a substituted or unsubstituted C3-C50 aromatic hydrocarbon group. 9 . The method of claim 8 , wherein in Chemical Formula 1, A and B are each independently a substituted or unsubstituted C3-C40 branched aliphatic hydrocarbon group, a substituted or unsubstituted C10-C60 straight-chain aliphatic hydrocarbon group, or a combination thereof.

10. The method of claim 1, wherein the semiconductor nanoparticles comprise a first organic ligand and a second organic ligand, the first organic ligand comprising a C12 or greater carboxylate moiety, the second organic ligand comprising a thiol moiety, and in a GC-MS analysis, the area of ​​the peak attributable to the second organic ligand is greater than or equal to 0.01% and less than or equal to 17% of the total area of ​​the peaks attributable to the first organic ligand and the second organic ligand.

11. Semiconductor nanoparticles including zinc, selenium, tellurium, and sulfur, wherein the semiconductor nanoparticles do not include cadmium, wherein the semiconductor nanoparticles are configured to emit blue light, wherein the semiconductor nanoparticles have an absolute quantum yield greater than or equal to 90%, and In the semiconductor nanoparticles, the molar ratio of zinc to selenium is greater than or equal to 1:1 and less than or equal to 3:1, and the molar ratio of sulfur to tellurium is greater than 73:1 and less than or equal to 180:

1.

12. The semiconductor nanoparticle of claim 11 , wherein the semiconductor nanoparticle comprises a first organic ligand and a second organic ligand, the first organic ligand comprising a C12 or greater carboxylate moiety, the second organic ligand comprising a thiol moiety, and in a GC-MS analysis, the area of ​​the peak attributable to the second organic ligand is greater than or equal to 0.01% and less than or equal to 17% of the total area of ​​the peaks attributable to the first organic ligand and the second organic ligand. 13 . The semiconductor nanoparticle of claim 12 , wherein in the GC-MS analysis, the area of ​​the peak attributed to the second organic ligand is less than or equal to 4% of the total area of ​​the peaks attributed to the first organic ligand and the second organic ligand.

14. The semiconductor nanoparticle according to claim 11, wherein the blue light has a peak emission wavelength greater than or equal to 450 nm and less than 480 nm; wherein the semiconductor nanoparticles have a size greater than or equal to 8 nm and less than or equal to 11 nm, and The semiconductor nanoparticles have a solidity greater than or equal to 0.

975.

15. The semiconductor nanoparticle according to claim 11, wherein in the semiconductor nanoparticle, The molar ratio of sulfur to tellurium (S:Te) is greater than or equal to 75:1 and less than or equal to 130:1, The molar ratio of zinc to selenium (Zn:Se) is greater than or equal to 1.5:1 and less than or equal to 1.9:1, The molar ratio of sulfur to the sum of selenium and sulfur (S:(S+Se)) is greater than or equal to 0.3:1 and less than or equal to 0.5:

1.

16. The semiconductor nanoparticle of claim 11, wherein the semiconductor nanoparticle has an absolute quantum yield greater than or equal to 95%.

17. The semiconductor nanoparticle of claim 15, comprising ZnTe x Se 1-x A first semiconductor nanocrystal, wherein x is greater than or equal to 0.005 and less than 0.

04.

18. An electroluminescent device comprising: a first electrode and a second electrode; and a light-emitting layer disposed between the first electrode and the second electrode, the light-emitting layer comprising the semiconductor nanoparticles according to any one of claims 11 to 17, and wherein the light-emitting layer is configured to emit blue light.

19. The electroluminescent device of claim 18, wherein the electroluminescent device is configured to exhibit a maximum external quantum efficiency greater than or equal to 10%, and wherein the electroluminescent device exhibits a T90 greater than or equal to 20 hours when operated at an initial brightness of 650 nits.

20. A display device comprising the electroluminescent device according to claim 18 or 19.

Citation Information

Patent Citations

  • Secure health verification using contactless cards

    KR1020230097055A